Resin mortar composition, laminate, and method for manufacturing laminate
Patent Information
- Application Number
- JP2024150790
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-13
- Filing Date
- 2024-09-02
- Publication Date
- 2025-03-26
AI Technical Summary
【0010】 本発明によれば、常温から低温の幅広い温度条件下において短時間での硬化が可能で、塗装後に硬化するまでの間に優れた流動性を有しつつ、かつ塗膜が硬化するまでの間に樹脂と骨材の分離を抑制することができる樹脂モルタル組成物、及び前記樹脂モルタル組成物を用いた積層体とその製造方法が提供される。
Smart Images

Figure 2025041549000006 
Figure 2025041549000007 
Figure 2025041549000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin mortar composition, a laminate, and a method for producing a laminate. [Background technology]
[0002] Conventionally, structures such as buildings and roads made of concrete or asphalt (hereinafter, these buildings and structures are referred to as "bases") are sometimes covered with resin mortar to impart functionality or for repair. For example, on bases such as floors, roads, and walls made of concrete or asphalt, a resin mortar layer made mainly of resin may be formed after a primer layer made mainly of resin is formed, or a resin mortar layer made mainly of resin may be formed directly without using a primer layer.
[0003] Resins used for the primer layer and the resin mortar include acrylic resin, vinyl ester resin, epoxy resin, urethane resin, unsaturated polyester resin, etc. Among these resins, acrylic resin and vinyl ester resin are formed by radical polymerization, have a fast curing speed, a moderate pot life, and excellent low-temperature curing and air curing properties, and therefore have the advantage of being able to shorten the construction period.
[0004] Resin mortar compositions have been proposed in which aggregate is mixed into a resin composition in order to improve the durability of coating films applied to substrates and the like. It is also known that the amount of aggregate mixed is increased to produce resin mortar compositions with good workability and finish in order to reduce hardening shrinkage. It has also been proposed to improve the cosmetic properties of hardened coating films by increasing the amount of aggregate and including a large amount of fine aggregate components (Patent Documents 1 and 2). However, there is a problem in that increasing the amount of aggregate easily increases viscosity, significantly reducing the fluidity of the resin mortar composition.
[0005] A resin mortar composition has also been proposed that can form a coating film with high strength and excellent adhesion to a topcoat layer by blending aggregate with a syrup composition containing a syrup containing a specific type and amount of monomer and a specific amount of wax (Patent Document 3). However, this resin mortar composition also has the problem that the viscosity tends to increase and the fluidity significantly decreases when the amount of aggregate is increased.
[0006] It has been proposed to use a mixture of ceramic aggregate and glass beads, because this allows the amount of aggregate to be increased in order to suppress hardening shrinkage, and also allows the permeability of the resin mortar composition into the concrete base to be well maintained (Patent Document 4). However, although the permeability of the resin mortar into the concrete base is increased and the fluidity of the resin mortar composition is obtained, there is a problem that the resin and aggregate components tend to separate. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 8-209058 [Patent Document 2] JP 2015-98527 A [Patent Document 3] JP 2013-7000 A [Patent Document 4] JP 2015-229683 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made to solve the above-mentioned problems, and has an object to provide a resin mortar composition that can be cured in a short time under a wide range of temperature conditions from room temperature to low temperature, has excellent fluidity after application until it is cured, and can suppress separation of the resin and aggregate until the coating film is cured, as well as a laminate using the resin mortar composition and a method for manufacturing the same. [Means for solving the problem]
[0009] The present invention includes the following configurations. [1] A resin mortar composition comprising 100 parts by mass of a resin composition (x) and 50 to 2,000 parts by mass of an aggregate (H), In 100% by mass of the aggregate (H), the proportion of aggregate having a particle diameter exceeding 1,180 μm is 0 to 1% by mass, the proportion of aggregate having a particle diameter exceeding 850 μm is 0 to 10% by mass, and the proportion of aggregate (h3) having a particle diameter exceeding 300 μm is 30 to 70% by mass; The integrated value (S3) of the specific surface area of the aggregate (h3) calculated by the following formula (1) is 25 to 70 cm 2 / g, The ratio R of the integrated value (S3) of the specific surface area to the integrated value (S) of the total specific surface area of the aggregate (H) calculated by the following formula (3) S3 The resin mortar composition according to claim 1, S3=6 / (D1×d×W1 / 100)+6 / (D2×d×W2 / 100)+6 / (D3×d×W3 / 100)+6 / (D4×d×W4 / 100)+6 / (D5×d×W5 / 100)...Formula (1) (In the above formula (1), S3 is the integrated value of the specific surface area (cm 2 / g), D1 = 300 (μm) / 10000 = 0.03 (cm), D2 = 450 (μm) / 10000 = 0.045 (cm), D3 = 600 (μm) / 10000 = 0.06 (cm), D4 = 850 (μm) / 10000 = 0.085 (cm), and D5 = 1180 (μm) / 10000 = 0.118 (cm). W1 to W5 are respectively the proportions (mass%) of the following aggregates (H5) to (H9) in the aggregate (H). d is the bulk density (g / cm 3 ) and can be determined by the following aggregate bulk density measurement method.) S=6 / (D6×d×W6 / 100)+6 / (D7×d×W7 / 100)+6 / (D8×d×W8 / 100)+6 / (D9×d×W9 / 100)+6 / (D 10 ×d×W 10 / 100)+6 / (D 11 ×d×W 11 / 100)+6 / (D 12 ×d×W 12 / 100)+6 / (D 13 ×d×W 13 / 100)+6 / (D 14 ×d×W 14 / 100)...Equation (3) (In the above formula (3), S is the integrated value (cm2) of the total specific surface area of the aggregate (H). 2 / g), D6=50(μm) / 10000=0.005(cm), D7=75(μm) / 10000=0.0075(cm), D8=106(μm) / 10000=0.0106(cm), D9=150(μm) / 10000=0.015(cm), D 10 = 300 (μm) / 10000 = 0.03 (cm), D 11 = 450 (μm) / 10000 = 0.045 (cm), D 12 = 600 (μm) / 10000 = 0.06 (cm), D 13 = 850 (μm) / 10000 = 0.085 (cm). W6~W 14 are the proportions (mass%) of the aggregates (H1) to (H9) in the aggregate (H), respectively. d is the bulk density (g / cm 3 ) and can be determined by the following aggregate bulk density measurement method.) Aggregate (H1): Aggregate having a particle size of 75 μm or less in the aggregate (H) Aggregate (H2): Aggregate having a particle size of more than 75 μm and not more than 106 μm in the aggregate (H) Aggregate (H3): Aggregate having a particle size of more than 106 μm and not more than 150 μm in the aggregate (H) Aggregate (H4): Aggregate having a particle size of more than 150 μm and not more than 300 μm in the aggregate (H) Aggregate (H5): Aggregate having a particle size of more than 300 μm and not more than 450 μm in the aggregate (H) Aggregate (H6): Aggregate having a particle size of more than 450 μm and not more than 600 μm in the aggregate (H) Aggregate (H7): Aggregate having a particle size of more than 600 μm and not more than 850 μm in the aggregate (H) Aggregate (H8): Aggregate with a particle size of more than 850 μm and less than 1,180 μm in the aggregate (H) Aggregate (H9): Aggregate with a particle size of more than 1,180 μm in the aggregate (H) (Method of measuring bulk density of aggregate) The aggregate (H) is passed through a sieve with 1.8 mm openings gently so as not to change its properties, and approximately 100 g is weighed out with an accuracy of 0.1% to prepare a sample. The mass of the sample is designated as M (g). The sample is gently placed in a dry 250 mL measuring cylinder (minimum graduation unit: 2 mL) without applying consolidation stress, and the filling volume (V0) is read to the minimum graduation unit, and the bulk density (d) (g / cm3) is calculated from the following formula (2). 3 ) is calculated. d=M / V0... Formula (2) [2] In 100% by mass of the aggregate (H), the proportion of aggregate (h1) having a particle diameter of 300 μm or less is 30 to 70% by mass, The aggregate (h1) contains the following aggregate (h2): The area ratio S of aggregate (h2) calculated by the following calculation method R The resin mortar composition according to [1], wherein the content of the carboxylic acid is 4 to 100%. Aggregate (h2): Aggregate in which the average circularity of all components of silicon, iron, magnesium, and aluminum analyzed using the image analysis method described below is 0.85 or higher. (Image analysis) A SEM (scanning electron microscope) image of the aggregate (h1) is taken, and elemental analysis is performed by EDS (energy dispersive X-ray spectroscopy) analysis for the same field of view of the SEM image, mapping is performed for each of the silicon, iron, magnesium, and aluminum that constitute the aggregate, and image analysis is performed using image processing software ImageJ (manufactured by the National Institutes of Health, USA) in the following steps (i) to (vi). Image analysis is performed using images converted to 8-bit map data. (i) Noise removal is performed using a Gaussian filter. (ii) Binarization is performed to create a binary image. (iii) The edges are smoothed using morphological operations. (iv) A filling process is carried out. (v) Carry out a split process. (vi) Obtain the area and circularity of the extracted particles. The image analysis is carried out three times, and the average value of the circularity values obtained is regarded as the "average circularity." (Area ratio of aggregate (h2) S R (Calculation method) In the image analysis of the SEM image and the map data of silicon, iron, magnesium, and aluminum in the same field of view in the steps (i) to (vi), the sum of the areas of the particles in the SEM image is S SEM The sum of the areas of particles with a circularity of 0.85 or more in the map data of silicon, iron, magnesium, and aluminum is defined as S Si , S Fe , S Mg , S Al Then, the area ratio S is calculated from the following equation (4). R The same operation is performed on three identical visual fields, and the area ratio S R ' average value of aggregate (h2) area ratio S R Let us assume that. S R '=(S Si +S Fe +S Mg +S Al ) / S SEM ×100...Formula (4) [3] The resin mortar composition according to [1] or [2], wherein the resin composition (x) contains at least one resin selected from the group consisting of acrylic resins and vinyl ester resins. [4] The resin mortar composition according to any one of [1] to [3], wherein the viscosity of the resin composition (x) measured at 23°C using a Brookfield viscometer (BM type) in accordance with the provisions of JIS Z 8803 is 5 to 1,000 mPa s. [5] The resin mortar composition according to any one of [1] to [4], further comprising an organic peroxide. [6] A method for producing a laminate, comprising coating the resin mortar composition according to [5] on a substrate and curing the resin mortar composition. [7] A laminate comprising a substrate and a cured coating film formed on the substrate and comprising a cured product of the resin mortar composition described in [5]. Effect of the Invention
[0010] According to the present invention, there is provided a resin mortar composition which can be hardened in a short time under a wide range of temperature conditions from room temperature to low temperature, has excellent fluidity after application until hardening, and can suppress separation of the resin and aggregate until the coating film hardens, as well as a laminate using the resin mortar composition and a method for producing the same. [Brief description of the drawings]
[0011] [Figure 1] 1 is a SEM image before processing in image analysis for measuring the circularity of aggregate (h1) having a particle diameter of 300 μm or less of aggregate (K-3) used in the examples. [Diagram 2] This is the SEM image of Figure 1 after Gaussian filter processing. [Diagram 3] 3 is an image obtained after image binarization processing of the image in FIG. 2. [Figure 4] This is the image of FIG. 3 after edge shaping. [Diagram 5] This is the image after filling processing of the image in FIG. [Figure 6] 6 is an image after the image in FIG. 5 has been segmented. [Figure 7] FIG. 7 is a measurement image of total aggregate area measurement obtained from the image in FIG. 6. [Figure 8] 1 is an EDS map data image before processing in image analysis for measuring the circularity of aggregate (h1) having a particle diameter of 300 μm or less of aggregate (K-3) used in the examples. [Figure 9] 9 is an image after 8-bit conversion processing of the EDS map data image of FIG. 8. [Figure 10] FIG. 10 is an image of FIG. 9 after Gaussian filtering. [Figure 11] 11 is an image obtained after image binarization processing of the image in FIG. 10. [Figure 12] 12 is an image after edge shaping of the image in FIG. 11. [Figure 13] 13 is an image after hole filling processing of the image in FIG. 12. [Figure 14] 14 is an image obtained after the image in FIG. 13 has been segmented. [Figure 15]16 is a measurement image of the circularity measurement obtained from the image of FIG. 15. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail. In the present invention, "(meth)acrylic" is a general term for acrylic and methacrylic. "(Meth)acrylate" is a general term for acrylate and methacrylate. "(Meth)acryloyl group" is a general term for acryloyl group and methacryloyl group, and is represented by the general formula CH2=C(R)-C(=O)-[R represents a hydrogen atom or a methyl group]. "(Meth)acrylic" is a general term for acrylic and methacrylic. The symbol "~" indicating a range of values means that the values before and after it are included as the lower and upper limits.
[0013] <Resin mortar composition> The resin mortar composition of the present invention comprises a resin composition (x) and an aggregate (H) blended therein.
[0014] <Resin composition (x)> The resin composition (x) preferably contains at least one resin selected from the group consisting of acrylic resins and vinyl ester resins. The components constituting the resin composition (x) are not particularly limited, but the below-described components (A) and (B), and optionally the component (C) and other additive components can be used.
[0015] [Component (A)] The component (A) is a monomer having one (meth)acryloyl group (hereinafter, also referred to as "monomer (A)"). The monomer (A) is a component that can adjust the viscosity of the resin composition (x) and adjust the mechanical strength of the cured coating film formed from the resin mortar composition. Examples of the monomer (A) include the following monomers (a1) to (a3). Among these, it is preferable to incorporate at least one of (a1) in order to easily adjust the viscosity of the resin composition (x) and to easily adjust the mechanical strength of the cured coating film formed from the resin mortar composition. Monomer (a1): a (meth)acrylate monomer having an alkyl group or a substituted alkyl group having 4 to 13 carbon atoms. Monomer (a2): Solubility parameter (hereinafter abbreviated as "SP value") is 9.5 (cal / cm 3 ) 1 / 2 The above (meth)acrylate monomers. Monomer (a3): A monomer (A) other than monomer (a1) and monomer (a2).
[0016] Specific examples of the monomer (a1) include n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, ethylene glycol monomethyl ether (meth)acrylate, ethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, 2-ethoxylated 2-ethylhexyl (meth)acrylate, polyethylene glycol monomethyl ether (meth)acrylate, polyethylene Glycidyl groups such as ethylene glycol monoethyl ether (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, polyethylene glycol mono(meth)acrylate (the number of repeating ethylene glycol units is 6 or less), polypropylene glycol mono(meth)acrylate (the number of repeating polypropylene glycol units is 4 or less), and glycidyl methacrylate Fluorine atom-containing (meth)acrylates such as trifluoroethyl (meth)acrylate, tetrafluoroethyl (meth)acrylate, hexafluoroethyl (meth)acrylate, and octafluoroethyl acrylate; (meth)acrylates having di- or trialkylcyclohexyl groups such as dimethylcyclohexyl (meth)acrylate and trimethylcyclohexyl (meth)acrylate; isobornyl methacrylate; dicyclopentenyloxyethyl (meth)acrylate; furyl (meth)acrylate, furfuryl (meth)acrylate, and (meth)acrylates having a furan ring, such as tetrahydrofuryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and caprolactone-modified tetrahydrofurfuryl (meth)acrylate; (meth)acrylates having a pyran ring, such as pyranyl (meth)acrylate; and (meth)acrylates having a hydropyran ring, such as dihydropyranyl (meth)acrylate, tetrahydropyranyl (meth)acrylate, dimethyldihydropyranyl (meth)acrylate, and dimethyltetrahydropyranyl (meth)acrylate. Among these, from the viewpoint of the mechanical properties of the cured product, it is preferable to use a (meth)acrylate having an alkyl group with 4 carbon atoms, such as n-butyl (meth)acrylate, i-butyl (meth)acrylate, or t-butyl (meth)acrylate, as the main component, and it is more preferable to use a (meth)acrylate having an alkyl group with 4 carbon atoms in combination with a (meth)acrylate having an alkyl group with 5 to 13 carbon atoms, such as 2-ethoxylated 2-ethylhexyl (meth)acrylate, polyethylene glycol monomethyl ether (meth)acrylate, polyethylene glycol monoethyl ether (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, or tridecyl (meth)acrylate.
[0017] The content of monomer (a1) is preferably 0 to 85 mass%, more preferably 0 to 80 mass%, and even more preferably 10 to 70 mass%, of 100 mass% in total of components (A), (B) and (C).
[0018] The resin composition (x) has an SP value of 9.5 (cal / cm 3 ) 1 / 2 It is preferable that the monomer contains a monomer having an SP value of 9.5 (cal / cm 3 ) 1 / 2 By including the above monomers, the compatibility of the monomer components is improved.
[0019] The SP value of the monomer (a2) means a value calculated by the method described in Polymer Engineering and Science, Vol. 14, by Robert F. Fedors et al. A specific example of the monomer (a2) is benzyl acrylate (SP value 10.1 (cal / cm 3 ) 1 / 2 ), benzyl methacrylate (SP value 10.0 (cal / cm 3 ) 1 / 2), cyclohexyl acrylate (SP value 9.7 (cal / cm 3 ) 1 / 2 ), cyclohexyl methacrylate (SP value 9.6 (cal / cm 3 ) 1 / 2 ), phenyl acrylate (SP value 10.1 (cal / cm 3 ) 1 / 2 ), phenyl methacrylate (SP value 9.7 (cal / cm 3 ) 1 / 2 ), phenoxyethyl acrylate (SP value = 10.1 (cal / cm 3 ) 1 / 2 ), phenoxyethyl methacrylate (SP value 9.7 (cal / cm 3 ) 1 / 2 ), phenoxy polyethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, phenoxy polypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, ethoxylated ortho-phenylphenol (meth)acrylate, phenol ethylene oxide (EO) modified acrylate, nonylphenol EO modified acrylate, phthalic acid 2-(meth)acryloyloxyethyl, hexahydrophthalic acid 2-(meth)acryloyloxyethyl, and other aromatic ring-containing (meth)acrylate monomers, such as maleic acid 2-(meth)acryloyloxyethyl, 2-hydroxyethyl acrylate (SP value 12.5 (cal / cm 3 ) 1 / 2 ), 2-hydroxyethyl methacrylate (SP value 12.1 (cal / cm 3 ) 1 / 2 ), 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate (SP value 11.5 (cal / cm 3 ) 1 / 2 ), 4-hydroxybutyl acrylate (SP value 11.6 (cal / cm 3 ) 1 / 2), hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, acryloylmorpholine (SP value 11.2 (cal / cm 3 ) 1 / 2 ), acetoacetoxyethyl methacrylate (SP value 11.2 (cal / cm 3 ) 1 / 2 ), hydroxyalkyl (meth)acrylate such as glycerin (meth)acrylate, 2-acryloyloxyethyl succinate (SP value 11.3 (cal / cm 3 ) 1 / 2 ), 2-methacryloyloxyethyl succinate, and the like. Among these, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl (meth)acrylate, acetoacetoxyethyl methacrylate, and 2-(meth)acryloyloxyethyl succinate are preferred, and benzyl (meth)acrylate, cyclohexyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl (meth)acrylate, and 2-(meth)acryloyloxyethyl succinate are more preferred.
[0020] The content of the monomer (a2) is preferably 0 to 85 mass%, more preferably 0 to 80 mass%, and even more preferably 10 to 70 mass%, of 100 mass% in total of the components (A), (B) and (C). The total content of the monomer (a1) and the monomer (a2) is preferably 55 to 85 mass % in the total of 100 mass % of the components (A), (B) and (C).
[0021] The resin composition (x) may contain a monomer (a3) other than the monomer (a1) and the monomer (a2). Specific examples of the monomer (a3) include methyl (meth)acrylate, ethyl (meth)acrylate, (meth)acrylic acid, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, polyethylene glycol mono(meth)acrylate (the number of repeating ethylene glycol units is 7 or more), and polypropylene glycol mono(meth)acrylate (the number of repeating polypropylene glycol units is 5 or more).
[0022] The content of the monomer (a3) is preferably 0 to 30 mass%, more preferably 0 to 20 mass%, and even more preferably 0 to 15 mass%, of 100 mass% in total of the components (A), (B) and (C).
[0023] The content of the (A) component is preferably 55 to 85 mass%, more preferably 60 to 85 mass%, of the total of 100 mass% of the (A), (B) and (C) components. When the content of the (A) component is equal to or more than the lower limit, the viscosity of the resin composition (x) does not become too high, and the coating workability is good. When the content of the (A) component is equal to or less than the upper limit, the viscosity of the resin composition (x) does not become too low, and the resin mortar composition can be appropriately prevented from unintentionally flowing out during work. The component (A) may be used alone or in combination of two or more types.
[0024] [(B) Component] The component (B) is one or more compounds selected from a monomer having two or more (meth)acryloyl groups, a urethane (meth)acrylate, an epoxy (meth)acrylate, a polyester (meth)acrylate, and a polymer component. As the component (B), the following components (b1), (b2) and (b3) can be used. Component (b1): A monomer having two or more (meth)acryloyl groups. Component (b2): an oligomer having two or more (meth)acryloyl groups. (b3) Component: polymer.
[0025] ((b1) component) The component (b1) can impart toughness to the cured coating film and can improve the mechanical strength of the cured coating film. Examples of the component (b1) include ethylene glycol di(meth)acrylate, 1,3-propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polybutylene glycol di(meth)acrylate, and bisphenol A ethylene oxide adduct di(meth). (meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether (meth)acrylic acid adduct, neopentyl glycol di(meth)acrylate, 1,4-cyclohexane dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(2-(meth)acryloyloxyethyl)isocyanurate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. Among these, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polybutylene glycol di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, etc. may be mentioned.
[0026] The content of component (b1) is preferably 0 to 20 mass%, more preferably 0 to 15 mass%, and even more preferably 0 to 10 mass%, of the total of 100 mass% of components (A), (B), and (C). When the content of component (b1) is equal to or less than the upper limit, the time until curing is not too short, coating workability is improved, and the toughness of the cured coating film is also improved.
[0027] ((b2) component) The component (b2) can improve the surface curability of the cured coating film and adjust the mechanical strength of the cured coating film. Examples of the component (b2) include urethane (meth)acrylate, epoxy (meth)acrylate, and polyester (meth)acrylate.
[0028] Examples of the urethane (meth)acrylate include a reaction product of a polyol, a polyisocyanate, and a (meth)acrylate having a hydroxyl group. Among them, from the viewpoint of improving the mechanical properties (elongation at break) of the cured product, a urethane (meth)acrylate having one or two (meth)acryloyl groups is preferred, and a reaction product of a diol, a diisocyanate, and a (meth)acrylate having a hydroxyl group is more preferred.
[0029] The polyol used to synthesize the urethane (meth)acrylate is a compound having two or more hydroxyl groups in one molecule. Examples of the polyol include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polybutylene glycol, and polyhexamethylene glycol; addition reaction products of dihydric phenols such as bisphenol A, bisphenol F, and bisphenol S with alkylene oxides such as ethylene oxide and propylene oxide; polyhydric alcohols such as ethylene glycol, propylene glycol, butanediol, butylene glycol, and methylpentanediol with phthalic acid, isophthalic acid, and tetrahydrophthalic acid; polyester diols obtained by reacting polybasic acids such as succinic acid, maleic acid, fumaric acid, adipic acid, sebacic acid, trimellitic acid, etc., and their anhydrides; polycaprolactone diols obtained from alkylene glycol and lactone; and polycarbonate diols having a carbonate bond obtained by reacting diols such as butanediol, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, cyclohexanedimethanol, etc., with carbonating agents such as phosgene, dimethyl carbonate, etc. The polyols may be used alone or in combination of two or more.
[0030] Among the polyols, from the viewpoint of mechanical properties (elongation at break) of the cured product, diol compounds having two hydroxyl groups are preferred. From the viewpoint of curability, polycarbonate diols are preferred, and polycarbonate diols synthesized using butanediol, pentanediol or hexanediol are more preferred. From the viewpoint of mechanical properties (elongation at break) of the cured product at low temperature, polyalkylene glycols, polyester diols, and polycaprolactone diols are preferred, and polyethylene glycol, polypropylene glycol, polybutylene glycol, polyester diol, and polycaprolactone diol are preferred.
[0031] The polyisocyanate used to synthesize the urethane (meth)acrylate is a compound having two or more isocyanate groups in one molecule. Examples of the polyisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, hexamethylene diisocyanate, tetramethylene diisocyanate, phenylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, and isophorone diisocyanate. These polyisocyanates may be used alone or in combination of two or more.
[0032] Examples of (meth)acrylates having a hydroxyl group used to synthesize urethane (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and an adduct of ε-caprolactone and 2-hydroxyethyl (meth)acrylate. The (meth)acrylates having a hydroxyl group may be used alone or in combination of two or more.
[0033] If necessary, an alcohol having an allyl group may be used instead of a (meth)acrylate having a hydroxyl group. Examples of the alcohol having an allyl group include allyl alcohol, ethylene glycol monoallyl ether, diethylene glycol monoallyl ether, polyethylene glycol monoallyl ether, propylene glycol monoallyl ether, dipropylene glycol monoallyl ether, polypropylene glycol monoallyl ether, and glycerin monoallyl ether.
[0034] The mass average molecular weight of the urethane (meth)acrylate is not particularly limited, but from the viewpoint of the mechanical properties (elongation at break) of the cured product, it is preferably 2,000 or more, and more preferably 5,000 or more. On the other hand, from the viewpoint of workability during coating, the mass average molecular weight of the urethane (meth)acrylate is preferably 30,000 or less, and more preferably 20,000 or less. In this specification, the mass average molecular weight of the urethane (meth)acrylate refers to a value obtained by dissolving the urethane (meth)acrylate in a solvent (tetrahydrofuran), measuring the molecular weight by gel permeation chromatography (GPC), and converting the measured molecular weight into polystyrene equivalent value.
[0035] Epoxy (meth)acrylate can be obtained, for example, by reacting an epoxy resin with (meth)acrylic acid. Examples of the epoxy resin include bisphenol type epoxy resin and novolac type epoxy resin.
[0036] The polyester (meth)acrylate can be obtained, for example, by reacting a polybasic acid or its anhydride, a polyhydric alcohol compound, and (meth)acrylic acid or glycidyl (meth)acrylate by a known method. Examples of the polybasic acid include phthalic acid, isophthalic acid, tetrahydrophthalic acid, succinic acid, maleic acid, fumaric acid, and adipic acid. Examples of the polybasic acid anhydride include the anhydrides of the above polybasic acids. Examples of the polyhydric alcohol include ethylene glycol and propylene glycol.
[0037] The molecular weight of the epoxy (meth)acrylate and polyester (meth)acrylate is preferably a mass average molecular weight of 30,000 or less from the viewpoint of workability during coating.
[0038] The amount of the component (b2) used is preferably 0 to 35 mass%, more preferably 0 to 30 mass%, and even more preferably 0 to 25 mass%, of 100 mass% consisting of the components (A), (B), and (C).
[0039] (Component (b3)) The component (b3) is a polymer. The component (b3) is a component that can improve the viscosity and curability of the resin composition (x). The polymer of the component (b3) preferably contains at least one of an acrylic polymer and a vinyl ester polymer. In addition, the component (b3) is preferably soluble in the components (A) and (b1).
[0040] The glass transition temperature (hereinafter abbreviated as "Tg") of the (b3) component is preferably 30°C or higher, more preferably 35 to 110°C, and even more preferably 40 to 90°C. When the (b3) component has a Tg of 30°C or higher, the surface curing property of the resin mortar composition is good. On the other hand, when the (b3) component has a Tg of 110°C or lower, the coating film can be prevented from becoming hard and brittle. In addition, when the resin mortar composition is produced, the solubility in the (A) component is good.
[0041] The Tg of the component (b3) means a value calculated by the following formula (5) based on the Fox formula. 1 / (273+Tg)=Σ(W n / (273+Tg n ))...Equation (5)
[0042] In formula (5), "Tg" is the glass transition temperature (°C) of component (b3). Component (b3) is a polymer of n types (n ≥ 1) of monomers (1), (2), (n), and "W n " is the mass fraction of the constituent units derived from each monomer constituting the (b3) component, and "Tg n " is the glass transition temperature (°C) of the homopolymer of the structural units derived from each monomer constituting the component (b3). For these glass transition temperatures, the values described in "Polymer Handbook 3rd Edition" (A WILEY-INTERSCIENCE PUBLICATION, 1989) can be used.
[0043] Examples of the component (b3) include the following polymers (b3-1) to (b3-4). (b3-1): one or more polymers selected from homopolymers of methyl methacrylate, copolymers of methyl methacrylate and other alkyl (meth)acrylates, and homopolymers and / or copolymers of other alkyl (meth)acrylates. (b3-2): A copolymer having at least one of a structural unit derived from methyl methacrylate and a structural unit derived from another alkyl (meth)acrylate, and a structural unit derived from a monomer having a double bond. (b3-3): Thermoplastic elastomers such as olefin-based thermoplastic elastomers, polybutadiene-based thermoplastic elastomers, styrene-butadiene thermoplastic elastomers, and styrene-isoprene thermoplastic elastomers. (b3-4): A vinyl chloride-vinyl acetate copolymer resin selected from a binary copolymer resin in which vinyl chloride and vinyl acetate are copolymerized, and a ternary copolymer resin in which vinyl chloride, vinyl acetate, and a functional group monomer (e.g., vinyl alcohol, dicarboxylic acid, hydroxyalkyl (meth)acrylate, etc.) are copolymerized. The component (b3) may contain only one of (b3-1), (b3-2), (b3-3) and (b3-4), or may contain two or more of them.
[0044] [Polymer (b3-1)] The polymer (b3-1) is one or more polymers selected from a homopolymer of methyl methacrylate, a copolymer of methyl methacrylate and other alkyl (meth)acrylates, and a homopolymer and / or copolymer of other alkyl (meth)acrylates. Other alkyl (meth)acrylates include methyl acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, ) acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, 2-dicyclopentenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, (meth)acrylic acid, and the like. The polymer (b3-1) may be used alone or in combination of two or more kinds.
[0045] The mass average molecular weight (hereinafter abbreviated as "Mw") of the polymer (b3-1) is preferably 10,000 to 200,000, more preferably 20,000 to 170,000, and even more preferably 30,000 to 170,000. By setting Mw to the lower limit or more, the strength of the cured coating film of the resin mortar composition can be improved. By setting Mw to the upper limit or less, the solubility in the (A) component and the (b1) component is improved when the resin mortar composition is produced. In this specification, the Mw of a polymer including the polymer (b3-1) means a value obtained by dissolving a resin in a solvent (tetrahydrofuran) and measuring the molecular weight by gel permeation chromatography (GPC) in terms of polystyrene.
[0046] The content of the polymer (b3-1) is preferably 1 to 25 mass%, more preferably 4 to 20 mass%, when the component (b-2) is not included, relative to the total 100 mass% of the (A), (B) and (C) components. In addition, the content of the polymer (b3-1) is preferably 0 to 25 mass%, more preferably 4 to 20 mass%, when the component (b-2) is included in an amount of 30 mass% or less, relative to the total 100 mass% of the (A), (B) and (C) components. If the content of the polymer (b3-1) is equal to or less than the upper limit, the pot life of the resin mortar composition (hereinafter, the time during which the composition has fluidity and can be used for painting) can be sufficiently secured, and the paint workability can be improved. On the other hand, if the content of the polymer (b3-1) is equal to or more than the lower limit, the viscosity balance of the resin composition (x) can be secured, and the curability can be improved, and the curing time can be appropriately shortened.
[0047] It is more preferable that the content of polymer (b3-1) is within the above-mentioned range and within a range that satisfies the following formula (6), based on 100% by mass of the total of components (A), (B), and (C). By satisfying formula (6), the viscosity of resin composition (x) does not become too high, and good coating workability can be maintained. 0<Mw of polymer (b3-1) × content of polymer (b3-1)<1,400,000 Equation (6) In formula (6), the "content of polymer (b3-1)" is the content (mass%) of polymer (b3-1) when the total of the components (A), (B), and (C) is 100 mass%.
[0048] When the polymer (b3-1) is a mixture of multiple polymers, it is preferable that the total value of the product of Mw and the content of each polymer satisfies the above formula (6). By satisfying the above formula (6), the viscosity of the resin composition (x) does not become too high, and good coating workability can be maintained.
[0049] [Polymer (b3-2)] The polymer (b3-2) is a copolymer having at least one of a structural unit derived from methyl methacrylate and a structural unit derived from another alkyl (meth)acrylate, and a structural unit derived from a monomer having a double bond. The double bond in the polymer (b3-2) is a double bond involved in a radical polymerization reaction, and examples of the functional group of the double bond include a vinyl group, an allyl group, a (meth)acryloyl group, etc. The polymer (b3-2) is a component that can improve the mechanical strength of the cured coating film of the resin mortar composition.
[0050] The polymer (b3-2) may have a structural unit derived from an acrylic monomer other than the structural unit derived from methyl methacrylate and the structural unit derived from a monomer having a double bond. Examples of the other acrylic monomer include a monofunctional acrylic monomer, a polyfunctional acrylic monomer, and (meth)acrylic acid.
[0051] Specific examples of other acrylic monomers include alkyl (meth)acrylates such as ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, sec-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; cycloalkyl (meth)acrylates such as isobornyl (meth)acrylate and cyclohexyl (meth)acrylate; and acrylic units not included in either the alkyl (meth)acrylate unit having an alkyl group with 2 or more carbon atoms or the cycloalkyl (meth)acrylate unit, such as glycidyl (meth)acrylate and (meth)acrylic acid. These may be used alone or in combination of two or more. Among the other acrylic monomers, alkyl methacrylates having an alkyl group with 2 to 4 carbon atoms, isobornyl (meth)acrylate, glycidyl (meth)acrylate, and (meth)acrylic acid are preferred. Among alkyl methacrylates having an alkyl group having 2 to 4 carbon atoms, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, and sec-butyl methacrylate are more preferable, and n-butyl methacrylate is even more preferable.
[0052] As the polymer (b3-2), a vinyl ester-based polymer which is a copolymer having at least one of a structural unit derived from methyl methacrylate and a structural unit derived from another alkyl (meth)acrylate, and a structural unit derived from a monomer having a double bond, and which has an ester bond, is more preferable.
[0053] The method for producing the polymer (b3-2) is not particularly limited, but the following production method is preferred. First, in the first stage reaction, methyl methacrylate, a first reactive monomer having a first functional group capable of forming an ester bond, and, if necessary, other acrylic monomers are copolymerized to obtain a first copolymer having the first functional group. Next, in the second stage reaction, a second reactive monomer having a second functional group and a double bond capable of reacting with the first functional group to form an ester bond is made to coexist with the first copolymer, and the first functional group and the second functional group are reacted to obtain a polymer (b3-2) having a structural unit derived from methyl methacrylate and a double bond. The combination of the first functional group and the second functional group is preferably a combination of a carboxy group and a glycidyl group, or a combination of a hydroxy group and an isocyanate group.
[0054] More specifically, the method for producing the polymer (b3-2) may be, for example, the following method. In the first stage reaction, methyl methacrylate, (meth)acrylic acid, and optionally other acrylic monomers are copolymerized to obtain a first copolymer having a carboxy group. Next, in the second stage reaction, the obtained first copolymer is dissolved in methyl methacrylate and then allowed to coexist with glycidyl (meth)acrylate. The carboxyl group of the first copolymer reacts with the glycidyl group of the glycidyl (meth)acrylate to form an ester bond, thereby obtaining a polymer (b3-2) having a double bond.
[0055] In the first stage reaction, the polymerization temperature and polymerization time for copolymerization vary depending on the polymerization method. For example, in the case of suspension polymerization, the temperature is preferably 70 to 98° C., and the polymerization time is preferably about 2 to 5 hours. The composition ratio of the monomers used in the first-stage reaction is preferably 0 to 99 mass% methyl methacrylate, 0 to 99 mass% other acrylic monomers, and 0.3 to 4 mass% (meth)acrylic acid, more preferably 0.3 to 2 mass% (meth)acrylic acid.
[0056] In the first stage reaction, when suspension polymerization is carried out as the polymerization method, the suspension is preferably an aqueous suspension. It is preferable to add a dispersant to the aqueous suspension. The dispersant is not particularly limited, and examples thereof include poorly water-soluble inorganic compounds such as calcium phosphate, aluminum hydroxide, starch powder, silica, etc.; nonionic polymer compounds such as polyvinyl alcohol, polyethylene oxide, cellulose derivatives, etc.; and anionic polymer compounds such as alkali metal salts of poly(meth)acrylic acid, and alkali metal salts of copolymers of (meth)acrylic acid and methyl (meth)acrylate. The amount of the dispersant added is preferably 0.005 to 5 mass %, and more preferably 0.01 to 1 mass %, based on the total mass of the suspension.
[0057] The suspension preferably contains an electrolyte such as sodium carbonate, sodium sulfate, manganese sulfate, etc. The inclusion of an electrolyte can improve the dispersion stability. The amount of electrolyte added may be appropriately determined and is not particularly limited.
[0058] In the suspension polymerization, it is preferable to use a polymerization initiator. Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, lauroyl peroxide, methyl ethyl ketone peroxide, tert-butyl peroxybenzoate, cumene hydroperoxide, cyclohexanone peroxide, dicumyl peroxide, and bis(4-tert-butylcyclohexyl)peroxydicarbonate; and azo compounds such as 2,2'-azobisisobutyronitrile and 2,2'-azobis-2-methylbutyronitrile. These may be used alone or in combination of two or more. The amount and method of adding the polymerization initiator are not particularly limited and may be appropriately determined.
[0059] In the suspension polymerization, it is preferable to use a chain transfer agent, which makes it possible to easily adjust the Mw of the resulting polymer. The chain transfer agent is preferably a thiol compound. Examples of the thiol compound include alkyl mercaptans such as t-butyl mercaptan, n-octyl mercaptan, and n-dodecyl mercaptan; aromatic mercaptans such as thiophenol thionaphthol; and alkyl thioglycolates such as thioglycolic acid and octyl thioglycolate. The amount and method of adding the chain transfer agent may be appropriately determined and are not particularly limited.
[0060] The Mw of the first copolymer obtained in the first stage reaction is preferably from 10,000 to 200,000, more preferably from 20,000 to 170,000, and even more preferably from 30,000 to 170,000. When the Mw of the first copolymer is equal to or greater than the lower limit, the strength of the cured product tends to be sufficiently high. When the Mw of the first copolymer is equal to or less than the upper limit, the workability of the resin mortar composition is improved.
[0061] The reaction temperature in the second stage reaction is preferably 90 to 95° C., and the reaction time is preferably about 1 to 4 hours. In the second stage reaction, the amount of methyl methacrylate monomer is preferably 70 to 150 parts by mass per 100 parts by mass of the first copolymer. Also, it is preferable to react 0.9 to 1.2 moles, and more preferably 1.0 to 1.1 moles, of glycidyl (meth)acrylate with 1.0 mole of (meth)acrylic acid used in the first stage reaction.
[0062] In the second stage reaction, an esterification catalyst can be used to promote the reaction between the first functional group and the second functional group. Examples of the esterification catalyst include amines such as triethylamine, quaternary ammonium salts such as tetraethylammonium chloride and tetrabutylammonium bromide, and phosphorus compounds such as triphenylphosphine. These may be used alone or in combination of two or more. The amount of the esterification catalyst added may be appropriately determined and is not particularly limited.
[0063] A polymerization inhibitor may be added in the second stage reaction. Adding a polymerization inhibitor can make the second stage reaction more stable. Examples of the polymerization inhibitor include hydroquinone, hydroquinone monomethyl ether, 2,6-di-t-butyl-4-methylphenol, etc. These may be used alone or in combination of two or more kinds. The amount of the polymerization inhibitor to be added may be appropriately determined and is not particularly limited.
[0064] The fact that the polymer (b3-2) obtained in the second-stage reaction has a double bond, i.e., that the carboxy group contained in the first copolymer has reacted with the glycidyl group of glycidyl (meth)acrylate in the second-stage reaction, can also be confirmed by the acid value of the polymer (b3-2) being lower than the acid value of the first copolymer. The acid value (unit: mgKOH / g) of the polymer (b3-2) is preferably 1.0 or less, and more preferably 0.5 or less. In this specification, the acid value of the polymer refers to a value determined by dissolving the polymer in toluene and titrating it with a 0.1 N KOH ethanol solution using phenolphthalein as an indicator.
[0065] The content of the polymer (b3-2) is preferably 1 to 25 mass%, more preferably 4 to 20 mass%, when the component (b-2) is not included, relative to the total 100 mass% of the (A), (B) and (C) components. In addition, the content of the polymer (b3-2) is preferably 0 to 25 mass%, more preferably 4 to 20 mass%, when the component (b-2) is included in an amount of 30 parts by mass or less, relative to the total 100 mass% of the (A), (B) and (C) components. When the content of the polymer (b3-2) is equal to or less than the upper limit, the pot life of the resin mortar composition can be sufficiently secured, and the coating workability can be improved. On the other hand, when the content of the polymer (b3-2) is equal to or more than the lower limit, the viscosity balance of the resin composition (x) is good, and the curability can be improved, and the curing time can be appropriately shortened.
[0066] The content of polymer (b3-2) is more preferably within the above range and satisfies the following formula (7) based on 100% by mass of the total of components (A), (B), and (C). By satisfying formula (7), the viscosity of resin composition (x) does not become too high, and coating workability can be improved. 0<Mw of polymer (b3-2) × content of polymer (b3-2)<1,400,000 Equation (7) In formula (7), the "content of polymer (b3-2)" is the content (mass%) of polymer (b3-2) when the total of the components (A), (B), and (C) is 100 mass%.
[0067] When the polymer (b3-2) is a mixture of multiple polymers, it is preferable that the total value of the product of Mw and the content of each polymer satisfies the above formula (7). By satisfying the above formula (7), the viscosity of the resin composition (x) does not become too high, and good coating workability can be maintained.
[0068] [Polymer (b3-3)] Examples of the elastomer component of the polymer (b3-3) include thermoplastic elastomers such as olefin-based thermoplastic elastomers, polybutadiene-based thermoplastic elastomers, styrene-butadiene thermoplastic elastomers, styrene-isoprene thermoplastic elastomers, etc. The structure of the elastomer component may be linear, branched, grafted, or core / shell.
[0069] The content of polymer (b3-3) is preferably less than 20% by mass relative to 100% by mass of the total of components (A), (B), and (C), and more preferably less than 20% by mass and satisfying the following formula (8): By satisfying formula (8), the viscosity of resin composition (x) does not become too high, and coating workability can be improved. 0<Mw of polymer (b3-3) × content of polymer (b3-3) < 1,400,000 ··· Equation (8) In formula (8), the "content of polymer (b3-3)" is the content (mass%) of polymer (b3-3) when the total of the components (A), (B), and (C) is 100 mass%.
[0070] [Polymer (b3-4)] The polymer (b3-4) is a vinyl chloride-vinyl acetate copolymer resin selected from a binary copolymer resin in which vinyl chloride and vinyl acetate are copolymerized, and a ternary copolymer resin in which vinyl chloride, vinyl acetate, and a functional group monomer (e.g., vinyl alcohol, dicarboxylic acid, hydroxyalkyl (meth)acrylate, etc.) are copolymerized. From the viewpoint of compatibility with each component, the polymer (b3-4) is preferably soluble in the component (A) and the component (b1). In order to obtain a cured coating film of the resin mortar composition having an excellent balance between tensile strength at break and tensile elongation at break, the proportion of vinyl acetate-derived structural units is preferably 1 to 35 mass%, the proportion of vinyl chloride-derived structural units is preferably 65 to 93 mass%, and the proportion of functional group monomer-derived structural units is preferably 0 to 13 mass%, based on 100 mass% of the solid content of the vinyl chloride-vinyl acetate copolymer resin. The binary copolymer resins and ternary copolymer resins may be used alone or in combination of two or more kinds.
[0071] The Mw of the vinyl chloride-vinyl acetate copolymer resin of the polymer (b3-4) is preferably 30,000 to 100,000, more preferably 35,000 to 80,000. When the Mw is equal to or greater than the lower limit, the strength of the cured coating film of the resin mortar composition can be improved. When the Mw is equal to or less than the upper limit, the solubility in the (A) and (b1) components is good when producing the resin mortar composition.
[0072] The content of the polymer (b3-4) is preferably 3 to 20 mass%, more preferably 5 to 15 mass%, when the composition does not contain any component (b3) other than the component (b2) and the polymer (b3-4) relative to the total 100 mass% of the components (A), (B), and (C). The content of the polymer (b3-4) is preferably 0 to 20 mass%, more preferably 0 to 15 mass%, and even more preferably 0 to 10 mass%, when the composition contains 30 mass% or less of the component (b2) and / or 20 mass% or less of the component (b3) other than the polymer (b3-4) relative to the total 100 mass% of the components (A), (B), and (C). If the content of the polymer (b3-4) is less than the upper limit, the pot life of the resin mortar composition can be sufficiently secured, and the coating workability can be improved. On the other hand, when the content of the polymer (b3-4) is equal to or more than the lower limit, the viscosity balance of the resin composition (x) is achieved, the curability thereof can be improved, and the curing time can be appropriately shortened.
[0073] The Tg of the polymer (b3-4) is preferably 50 to 90°C or higher, more preferably 55 to 80°C. When the Tg of the polymer (b3-4) is equal to or higher than the lower limit, the surface curing property of the resin mortar composition is good. On the other hand, when the Tg of the polymer (b3-4) is equal to or lower than the upper limit, the cured coating film can be prevented from becoming hard and brittle. In addition, when the resin mortar composition is produced, the solubility in the (A) component is good.
[0074] The content of component (b3) is preferably 1 to 25 mass%, more preferably 4 to 20 mass%, relative to 100 mass% of the total of components (A), (B), and (C) when component (b-2) is not included. Also, the content of component (b3) is preferably 0 to 25 mass%, more preferably 4 to 20 mass%, relative to 100 mass% of the total of components (A), (B), and (C) when component (b-2) is 30 mass% or less. If the content of the (b3) component is equal to or less than the upper limit, the resin mortar composition can have a sufficient pot life and can be easily applied. On the other hand, if the content of the (b3) component is equal to or more than the lower limit, the viscosity balance of the resin composition (x) is good, and the curability is improved, thereby shortening the curing time appropriately.
[0075] When the component (b3) is a mixture of two or more of the polymers (b3-1), (b3-2), (b3-3), and (b3-4), it is preferable that the following formula (9) is satisfied. By satisfying the following formula (9), the viscosity of the resin composition (x) does not become too high, and coating workability can be improved. 0<{Mw of polymer (b3-1) × content of polymer (b3-1)} + {Mw of polymer (b3-2) × content of polymer (b3-2)} + {Mw of polymer (b3-3) × content of polymer (b3-3)} + {Mw of polymer (b3-4) × content of polymer (b3-4)} < 1,400,000 ··· (9)
[0076] The content of the (B) component is preferably 15 to 35 mass%, more preferably 20 to 35 mass%, based on 100 mass% of the total of the (A), (B) and (C) components. By making the content of the (B) component equal to or more than the lower limit, the viscosity of the resin composition (x) does not become too low, separation from the aggregate does not occur, and workability becomes good. By making the content of the (B) component equal to or less than 35 parts by mass, the viscosity of the resin composition (x) does not become too high, and workability becomes good and the adhesive strength to the substrate can be improved.
[0077] [(C) component] Component (C) is a plasticizer that can reduce the shrinkage of the coating film during curing. Examples of the plasticizer include phthalates such as dibutyl phthalate, di-2-ethylhexyl phthalate, and diisodecyl phthalate; adipic esters such as di-2-ethylhexyl adipate and octyl adipate; sebacic esters such as dibutyl sebacate and di-2-ethylhexyl sebacate; dibasic fatty acid esters such as azelaic esters such as di-2-ethylhexyl azelate and octyl azelate; acetyl tributyl citrate; paraffins such as chlorinated paraffin, normal paraffin, and paraffin wax; and alkylsulfonic acid phenyl ester. From the viewpoint of increasing the mechanical properties (elongation at break) of the cured coating film, the plasticizer is preferably a phthalate, an adipic ester, a paraffin, or an alkylsulfonic acid phenyl ester, and more preferably an adipic ester, a paraffin, or an alkylsulfonic acid phenyl ester. The plasticizer may be used alone or in combination of two or more kinds.
[0078] The content of the plasticizer is preferably 0 to 20 parts by mass, more preferably 0 to 15 parts by mass, based on 100 parts by mass of the total of the components (A), (B), and (C). When the content of the plasticizer is within the above range, the mechanical strength of the cured coating film can be improved, and the exudation of the plasticizer to the surface of the cured coating film can be prevented.
[0079] [Other additives] Other additive components that can be used in the resin composition (x) as needed include wax, curing accelerator, curing agent, polymerization inhibitor, silane coupling agent, ultraviolet absorber, light resistance stabilizer, thixotropic agent, reinforcing material, other polymer components, isocyanate prepolymer, thiol compound, inorganic pigments such as chromium oxide and red iron oxide, organic pigments such as phthalocyanine blue, etc. In addition, the resin composition (x) can also contain, as additive components, antifoaming agents, defoaming agents, leveling agents, etc. for the purpose of improving coating workability and appearance, etc.
[0080] (wax) The wax is a component that improves surface curing by blocking air on the coating surface during the curing reaction. Wax that does not dissolve in components (A) and (B) can be used. Specific examples of waxes include paraffins, polyethylenes, and higher fatty acids such as stearic acid. From the viewpoint of air barrier properties, paraffin wax is preferred. The melting point of the wax is preferably 40° C. or higher and 120° C. or lower. Two or more waxes having different melting points can be used in combination.
[0081] The wax may be a wax dispersed in an organic solvent in order to improve surface curability. The wax is dispersed in an organic solvent and is microparticulated, so that the air barrier effect can be effectively exhibited. The wax in this dispersed state can be a commercially available product, and the resin composition (x) can be prepared by adding the wax as it is. In this case, the resin composition (x) also contains an organic solvent. The dispersed wax may be one in which the wax is dispersed in the components (A) and (B) without containing any organic solvent.
[0082] From the viewpoint of the balance between the air barrier effect and the physical properties of the coating film, the content of the wax is preferably 0.1 to 3 parts by mass, and more preferably 0.1 to 2 parts by mass, per 100 parts by mass of the total of the components (A), (B) and (C). If the wax content is equal to or greater than the lower limit, sufficient air barrier effect can be obtained when the resin mortar composition is applied and cured, and surface curability can be improved. If the wax content is equal to or less than the upper limit, the viscosity of the resin composition (x) does not become too high, and the physical properties of the coating film, such as the curing speed and the stain resistance, tend to be good. In addition, the storage stability of the resin mortar composition is good.
[0083] (Cure accelerator) The resin composition (x) preferably contains a curing accelerator. Examples of the curing accelerator include tertiary amines, organometallic compounds, and metal soaps. Specific examples of tertiary amines include N,N-substituted anilines such as N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, 4-(N,N-dimethylamino)benzaldehyde, 4-[N,N-bis(2-hydroxyethyl)amino]benzaldehyde, 4-(N-methyl-N-hydroxyethylamino)benzaldehyde, N,N-bis(2-hydroxypropyl)-p-toluidine, triethanolamine, diethylenetriamine, phenylmorpholine, N,N-bis(hydroxyethyl)aniline, and diethanolaniline, N,N-substituted-p-toluidines, and 4-(N,N-substituted amino)benzaldehyde. The tertiary amines may be used alone or in combination of two or more kinds.
[0084] Among the tertiary amines, aromatic tertiary amines are preferred. As the aromatic tertiary amine, a compound having at least one aromatic residue directly bonded to a nitrogen atom is preferred. Examples of the aromatic tertiary amine include N,N-dimethyl-p-toluidine, N,N-diethylaniline, N,N-diethyl-p-toluidine, N-(2-hydroxyethyl)N-methyl-p-toluidine, N,N-di(2-hydroxyethyl)-p-toluidine, N,N-di(2-hydroxypropyl)-p-toluidine; ethylene oxide or propylene oxide adducts of N,N-di(2-hydroxyethyl)-p-toluidine or N,N-di(2-hydroxypropyl)-p-toluidine, and o (ortho) and m (meta) forms thereof. Among the aromatic tertiary amines, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-di(2-hydroxyethyl)-p-toluidine and N,N-di(2-hydroxypropyl)-p-toluidine are preferred from the viewpoint of the curability of the resin composition.
[0085] Examples of the organometallic compound include cobalt naphthenate, manganese naphthenate, nickel octylate, cobalt octylate, and cobalt acetoacetylate. By adding these organometallic compounds to the resin composition, the surface curing property can be improved. The organometallic compounds may be used alone or in combination of two or more.
[0086] The amount of the curing accelerator added is preferably 0.05 to 10 parts by mass, more preferably 0.2 to 8 parts by mass, and even more preferably 0.3 to 5 parts by mass, relative to 100 parts by mass of the total of the components (A), (B), and (C) from the viewpoint of the balance between curability and workability, etc. If the amount of the curing accelerator added is equal to or more than the lower limit, the surface curability can be improved, and if it is equal to or less than the upper limit, an appropriate pot life can be achieved even at low temperatures. The amount of the curing accelerator to be added is preferably adjusted appropriately depending on the type of the curing accelerator to be used and the temperature environment.
[0087] With regard to the amount of the organometallic compound added, in terms of the balance between curability and workability, the content of the metal derived from the organometallic compound is preferably 0.3 parts by mass or less, and more preferably 0.2 parts by mass or less, per 100 parts by mass of the total of the components (A), (B), and (C). The amount of the organometallic compound added is preferably adjusted appropriately depending on the type of curing accelerator used and the temperature environment.
[0088] The hardening accelerator may be added immediately before hardening the resin mortar composition, or may be added to the resin mortar composition in advance.
[0089] (hardening agent) When curing the resin mortar composition, it is preferable to use the above-mentioned curing accelerator in combination with a curing agent as a redox catalyst. As the curing agent, a known curing agent capable of initiating radical polymerization can be used. Specific examples of the curing agent include ketone peroxides such as methyl ethyl ketone peroxide; peroxyketals such as 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-hexylperoxy)cyclohexane, and 1,1-di(t-butylperoxy)cyclohexane; hydroperoxides such as 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and p-menthane hydroperoxide; dicumyl peroxide; Examples of the curing agent include dialkyl peroxides such as di-t-butyl peroxide, diacyl peroxides such as dilauroyl peroxide and dibenzoyl peroxide, peroxydicarbonates such as di(4-t-butylcyclohexyl)peroxydicarbonate and di(2-ethylhexyl)peroxydicarbonate, and peroxyesters such as t-butylperoxy-2-ethylhexanoate, t-hexylperoxyisopropyl monocarbonate and t-butylperoxybenzoate. One type of curing agent may be used alone, or two or more types may be used in combination.
[0090] As the curing agent, organic peroxides are preferred, and among them, diacyl peroxides, peroxy esters and hydroperoxides are more preferred, and benzoyl peroxide is even more preferred. From the viewpoint of ease of handling, benzoyl peroxide is preferably in the form of a liquid diluted with an inert liquid or solid to a concentration of about 30 to 55 mass %, a paste, or a powder.
[0091] The amount of the hardener added is preferably adjusted so that the pot life of the resin mortar composition is 10 to 60 minutes. If the hardener is added in the amount described above, the polymerization reaction starts immediately after the addition, and the hardening of the resin mortar composition can be promoted. When benzoyl peroxide is used as a curing agent, the amount added is preferably 0.25 to 10 parts by mass, more preferably 0.25 to 8 parts by mass, and even more preferably 0.25 to 6 parts by mass, relative to 100 parts by mass of the total of the (A), (B) and (C) components. When the amount of benzoyl peroxide added is equal to or more than the lower limit, the curing property becomes good, and when the amount is equal to or less than the upper limit, the coating workability of the resin mortar composition and various physical properties of the resulting coating film tend to be improved. However, it is preferable to appropriately adjust the amount of the curing agent added depending on the temperature of use.
[0092] (Polymerization inhibitor) As the polymerization inhibitor, from the viewpoint of improving storage stability, hydroquinone, 2-methylhydroquinone, hydroquinone monomethyl ether, 2-6-di-t-butyl-4-methylphenol, etc. are preferable. These may be used alone or in combination of two or more kinds.
[0093] (Silane coupling agent) The silane coupling agent can be used for the purpose of improving adhesion to inorganic substances. Examples of the silane coupling agent include silane coupling agents having one (meth)acryloyl group, such as γ-(glycidoxypropyl)trimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, etc. These may be used alone or in combination of two or more.
[0094] The content of the silane coupling agent is preferably 5 parts by mass or less, and from the viewpoints of curability and cost, more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, per 100 parts by mass of the total of the (A), (B) and (C) components. By making the content of the silane coupling agent equal to or less than the upper limit, the adhesion to inorganic components and surface curability of the resin mortar composition can be improved.
[0095] (UV absorber) The ultraviolet absorber is used for the purpose of improving the weather resistance of the coating film. Examples of the ultraviolet absorber include derivatives of 2-hydroxybenzophenone such as 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-octyloxybenzophenone, 2-hydroxy-4-decyloxybenzophenone, 2-hydroxy-4,4'-dimethoxybenzophenone, and 2-hydroxy-4,4'-dibutoxybenzophenone; 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-ditertiarybutylphenyl)benzotriazole or halides thereof; phenyl salicylate, p-tertiarybutylphenyl salicylate, etc. These may be used alone or in combination of two or more.
[0096] (Light resistance stabilizer) As the light resistance stabilizer, for example, a hindered amine light stabilizer (HALS) can be used. As the light resistance stabilizer, bis(2,2,6,6,-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6,-pentamethyl-4-piperidyl)sebacate, 1-[2-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy]ethyl]-4-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy]-2,2,6,6,-tetramethylpiperidine, 4-benzoyloxy-2,2,6,6,-tetramethylpiperidine, etc. can be used alone or in combination of two or more.
[0097] (thixotropic agent) The thixotropic agent is an additive component that imparts thixotropy to the resin mortar composition. Specifically, when the thixotropic agent is contained, structural viscosity is imparted to the resin mortar composition, the thixotropy is increased, and the additives in the resin mortar composition can be uniformly distributed, thereby improving the storage stability of the resin mortar composition. In addition, when the thixotropic agent is contained, the resin mortar composition can be improved in coating workability, for example, when applied to an inclined surface.
[0098] As the thixotropic agent, organic thixotropic agents such as urethane urea, fatty acid amide, organic bentonite, oxidized polyethylene wax, and fine silica are preferable. The thixotropic agent may be used alone or in combination of two or more kinds. Examples of combinations of thixotropic agents include a combination of fatty acid amide and fine silica, a combination of organic bentonite and fine silica, a combination of fatty acid amide, organic bentonite and fine silica, and a combination of oxidized polyethylene wax and fine silica. From the viewpoint of dispersion stability in the resin mortar composition, the average primary particle size of the fine silica is preferably 7 to 40 μm.
[0099] When the thixotropic agent is at least one of urethane urea, fatty acid amide, and organic bentonite, the content of the thixotropic agent is preferably 5 parts by mass or less per 100 parts by mass of the total of components (A), (B), and (C). When the thixotropic agent is particulate silica, the content of the particulate silica is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less per 100 parts by mass of the total of components (A), (B), and (C). When the content of the thixotropic agent is equal to or less than the upper limit, the fluidity of the resin mortar composition is less likely to decrease, and coating workability is easily ensured, making it easier to obtain a uniform coating film.
[0100] (Reinforcement) The reinforcing material is preferably used when the flexibility or tensile elongation at break of the resin mortar composition is excessive for the scene of use. Examples of the reinforcing material include chopped strands, glass fibers in the form of a roving net, vinylon fibers, nylon fibers, etc. The reinforcing material may be used alone or in combination of two or more kinds.
[0101] (Other polymer components) The resin composition (x) may contain other polymer components in addition to the (b2) and (b3) components. Examples of the other polymer components include elastomers other than the polymer (b3-3) and epoxy resins. The content of the other polymer components is preferably adjusted appropriately so as not to impair the transparency of the cured product.
[0102] Epoxy resin is a component that improves adhesion to inorganic substrates, and therefore, if the resin mortar composition contains an epoxy resin, it can improve adhesion to crushed stone and the like used in concrete and asphalt pavement. Examples of the epoxy resin include bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, polysulfide modified epoxy resin, etc. The epoxy resin may be used alone or in combination of two or more kinds.
[0103] The content of the epoxy resin is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the total of the (A), (B) and (C) components. When the content of the epoxy resin is equal to or less than the upper limit, the curing time can be shortened while the pot life of the resin mortar composition is sufficiently ensured, and the workability is improved.
[0104] [Isocyanate prepolymer] The isocyanate prepolymer is highly reactive and easily reacts with moisture in the air and monomer components in the resin mortar composition, so if the resin mortar composition contains the isocyanate prepolymer, the curing time can be further shortened. Examples of the isocyanate prepolymer include polyisocyanurates obtained by prepolymerizing hexamethylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, tetramethylene diisocyanate, phenylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, isophorone diisocyanate, etc. One type of isocyanate prepolymer may be used alone, or two or more types may be used in combination.
[0105] The content of the isocyanate prepolymer is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, based on 100 parts by mass of the total of the (A), (B) and (C) components. When the content of the isocyanate prepolymer is equal to or less than the upper limit, the curing time can be shortened while the pot life of the resin mortar composition is sufficiently ensured, and the workability is improved.
[0106] (Thiol compounds) The resin composition (x) may contain a thiol compound. Examples of the thiol compound include aromatic thiophenols and aliphatic thiols. Among these, it is preferable to contain an aliphatic thiol. Among the thiol compounds, one or more thiol compounds selected from primary thiol compounds, secondary thiol compounds, and tertiary thiol compounds can be used. By blending a thiol compound in the present invention, the curability of the cured coating film can be improved. The thiol compound is not particularly limited as long as it has one or more thiol groups in the molecule, but from the viewpoint of the curing property of the thin film that is easily affected by oxygen in the air, a multifunctional thiol, which is a compound having two or more primary or secondary thiol groups in the molecule, is preferred. Among them, a multifunctional thiol, which is a compound having three or more primary or secondary thiol groups in the molecule, is more preferred. The polyfunctional thiol refers to a thiol compound having two or more thiol groups, which are functional groups, in the molecule.
[0107] Specific examples of primary thiol compounds include trimethylolpropane tris-mercaptoacetate, trimethylolpropane tris-(3-mercaptopropionate), trimethylolpropane tris-(4-mercaptobutyrate), pentaerythritol tetramercaptoacetate, pentaerythritol tetrakis-(3-mercaptopropionate), pentaerythritol tetrakis-(4-mercaptobutyrate), dipentaerythritol hexamercaptoacetate, dipentaerythritol hexakis-(3-mercaptopropionate), dipentaerythritol hexakis-(4-mercaptobutyrate), glycerol tris-(3-mercaptopropionate), glycerol tris-(4-mercaptobutyrate), tetraethylene glycol bismercaptoacetate, and tetraethylene glycol. Examples of the isocyanurate include bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptobutyrate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, and tris-[(3-mercaptobutyryloxy)-ethyl]-isocyanurate.
[0108] Specific examples of secondary thiol compounds include 3-mercaptobutyric acid, ethylene glycol bis(3-mercaptobutyrate), propylene glycol bis(3-mercaptobutyrate), diethylene glycol bis(3-mercaptobutyrate), butanediol bis(3-mercaptobutyrate), octanediol bis(3-mercaptobutyrate), trimethylolethane tris(3-mercaptopropionate), trimethylolethane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptobutyrate), ethylene glycol bis(2-mercaptopropionate), propylene glycol bis(2-mercaptobutyrate), captopropionate), diethylene glycol bis(2-mercaptopropionate), butanediol bis(2-mercaptopropionate), octanediol bis(2-mercaptopropionate), trimethylolpropane tris(2-mercaptopropionate), pentaerythritol tetrakis(2-mercaptopropionate), dipentaerythritol hexakis(2-mercaptopropionate), ethylene glycol bis(4-mercaptovalerate), diethylene glycol bis(4-mercaptovalerate), butanediol bis(4-mercaptovalerate), 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris[2-(3-mercaptobutyryloxyethyl)]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, octanediol bis(4-mercaptovalerate), trimethylolpropane tris(4-mercaptovalerate), pentaerythritol tetrakis(4-mercaptovalerate), dipentaerythritol hexakis(4-mercaptovalerate), ethylene glycol bis(3-mercaptovalerate), propylene glycol bis(3-mercaptovalerate), diethylene glycol bis(3-mercaptovalerate), butanediol bis(3-mercaptovalerate), octanediol bis(3-mercaptovalerate), trimethylolpropane tris(3-mercaptovalerate), pentaerythritol tetrakis(3-mercaptovalerate), dipentaerythritol hexakis(3-mercaptovalerate), hydrogenated bisphenol A bis(3-mercaptobutyrate), bi Examples of the esters include phenol A dihydroxyethyl ether-3-mercaptobutyrate, ethylene glycol bis(3-mercapto-3-phenylpropionate), propylene glycol bis(3-mercapto-3-phenylpropionate), diethylene glycol bis(3-mercapto-3-phenylpropionate), butanediol bis(3-mercapto-3-phenylpropionate), octanediol bis(3-mercapto-3-phenylpropionate), trimethylolpropane tris(3-mercapto-3-phenylpropionate), tris-2-(3-mercapto-3-phenylpropionate)ethyl isocyanurate, pentaerythritol tetrakis(3-mercapto-3-phenylpropionate), and dipentaerythritol hexakis(3-mercapto-3-phenylpropionate). Among them, from the viewpoint of the hardening property of the resin mortar composition, 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris[2-(3-mercaptobutyryloxyethyl)]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), and trimethylolpropane tris(3-mercaptobutyrate) are preferred. These may be used alone or in combination of two or more.
[0109] The molecular weight of the thiol compound used in the present invention is preferably 200 to 1,000.
[0110] The content of the thiol compound is preferably 0.05 to 2 parts by mass, more preferably 0.1 to 1.5 parts by mass, based on 100 parts by mass of the total of the components (A), (B) and (C). When the content of the thiol compound is equal to or more than the lower limit, the surface curability is good when cured in a thin layer, and when the content is equal to or less than the upper limit, the amount of the thiol compound used can be reduced when cured in a thin layer. The thiol compound may be used alone or in combination of two or more kinds. A primary thiol compound and a secondary thiol compound may be used in combination.
[0111] (Antifoaming agent) The defoaming agent may be a known defoaming agent, specifically, an acrylic defoaming agent obtained by dissolving a special acrylic polymer in a solvent, a vinyl defoaming agent obtained by dissolving a special vinyl polymer in a solvent, etc. Among the defoamers, acrylic defoamers obtained by dissolving special acrylic polymers in a solvent are preferred, and examples thereof include the Disparlon series (product names: OX-880EF, OX-881, OX-883, OX-77EF, OX-710, OX-8040, 1922, 1927, 1950, P-410EF, P-420, P-425, PD-7, 1970, 230, 230EF, LF-1980, LF-1982, LF-1983, LF-1984, LF-1985, etc.) available from Kusumoto Chemical Co., Ltd. are more preferred, and among the Disparlon series, 230, 230EF, LF-1980, and LF-1985 are even more preferred. In addition, BYK-052N, BYK-1752, etc. available from BYK Japan Co., Ltd. can also be used. The antifoaming agent may be used alone or in combination of two or more kinds.
[0112] The content of the defoaming agent is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, based on 100 parts by mass of the total of the (A), (B) and (C) components. When the content is equal to or less than the upper limit, air bubbles mixed in when the resin mortar composition is stirred and mixed can be effectively removed, and a coating film free of air bubbles can be obtained.
[0113] The viscosity of the resin composition (x) measured at 23°C using a Brookfield viscometer (BM type) in accordance with the provisions of JIS Z 8803 is preferably 5 to 1,000 mPa·s, more preferably 5 to 500 mPa·s, even more preferably 10 to 300 mPa·s, and particularly preferably 10 to 150 mPa·s. If the viscosity of the resin composition (x) is within the above range, the higher the viscosity, the more the dripping during coating can be prevented, and the lower the viscosity, the better the workability during coating.
[0114] The flash point of the resin composition (x) is preferably 15° C. or higher. In the present invention, the flash point of the resin composition (x) means the flash point of the radical polymerizable compound having the lowest flash point (minimum flash point) among the radical polymerizable compounds (component (A) and component (B)) contained in the resin composition (x).
[0115] <Aggregate (H)> The aggregate (H) used in the resin mortar composition of the present invention is a component that imparts strength to the cured coating film obtained from the resin mortar composition and is added as an extender. Examples of aggregate (H) include natural inorganic minerals such as sand, silica sand, river sand, kansui stone, emery, and marble; alumina, slag, glass, ceramic aggregate, pottery, porcelain, tile, glass beads, colored aggregate, calcium carbonate, silica fume, fly ash, talc, clay, titanium oxide, aluminum hydroxide, etc. One type of aggregate (H) may be used alone, or two or more types may be used in combination. Furthermore, when transparency of the cured product is required, the material may be appropriately selected from natural inorganic minerals such as sand, silica sand, river sand, kansui stone, emery, and marble; alumina, slag, glass, ceramic aggregate, pottery, porcelain, tile, glass beads, colored aggregate, and the like.
[0116] In the present invention, the term "fluidity" refers to the property of an uncured resin mortar composition obtained by mixing the resin composition (x) and aggregate (H) to wet and spread on a base. The fluidity of the resin mortar composition is not obtained only by the viscosity of the resin composition (x) or the viscosity of the resin mortar composition. It can be obtained by mixing the resin composition (x) and aggregate (H) of a specific composition in a predetermined mass ratio.
[0117] The aggregate (H) is composed of aggregate (h1) having a particle diameter of 300 μm or less and aggregate (h3) having a particle diameter of more than 300 μm. In 100% by mass of aggregate (H), the proportion of aggregate (h1) is 30 to 70% by mass, and the proportion of aggregate (h3) is 30 to 70% by mass.
[0118] [Aggregate (h1)] The aggregate (h1) preferably contains the following aggregate (h2). Aggregate (h2): Aggregate in which the average circularity of all components of silicon, iron, magnesium, and aluminum analyzed is 0.85 or higher when the image analysis described below is performed.
[0119] (Image analysis) A SEM (scanning electron microscope) image of the aggregate (h1) is taken, and elemental analysis is performed by EDS (energy dispersive X-ray spectroscopy) analysis for the same field of view of the SEM image, mapping is performed for each of the silicon, iron, and magnesium that compose the aggregate, and the image is analyzed using the image processing software ImageJ (manufactured by the National Institutes of Health, USA) in the following steps (i) to (vi). Image analysis is performed using images converted to 8-bit map data. (i) Noise removal is performed using a Gaussian filter. (ii) Binarization is performed to create a binary image. (iii) The edges are smoothed using morphological operations. (iv) A filling process is carried out. (v) Carry out a split process. (vi) Obtain the area and circularity of the extracted particles. However, image analysis is performed using SEM images in which the ratio of the total area of particles to the total area of the acquired image is 20 to 50%.
[0120] For image analysis, the following devices and conditions can be applied, for example. (SEM observation) Equipment: Hitachi S-3400N Scanning Electron Microscope SEM image acquisition conditions A) Acceleration voltage: 5 kV B) Magnification: ×300 (EDS analysis) Equipment: Oxford Instruments AZtecLive ULTIM MAX40 Map data acquisition conditions A) Acceleration voltage: 5 kV B) Magnification: ×300 C) Mapping resolution: 1024 D) Number of frames: 30 E) Duel time: 100μs F) Process time: 4
[0121] "Circularity" is a number that indicates the complexity of a figure drawn in an image, etc. A perfect circle has a maximum value of 1, and shapes other than a perfect circle have a value less than 1. The more complex the figure, the smaller the number becomes. Circularity can be calculated using the following formula (10). Circularity = 4π × S A ÷L A 2 ··· Equation (10) In the formula (10), S A is the area of the target figure, and L A is the perimeter of the target shape. The average circularity of the aggregate obtained by performing image analysis multiple times is defined as the "average circularity."
[0122] An aggregate, for which the average circularity of the silicon map data, the average circularity of the iron map data, the average circularity of the magnesium map data, and the average circularity of the aluminum map data obtained by the image analysis of the same field of view of the SEM image are all 0.85 or more, is defined as aggregate (h2). The average circularity of the aggregate (h2) is preferably 0.85 or more, more preferably 0.9 or more, and even more preferably 0.95 or more.
[0123] The area ratio S of aggregate (h2) calculated using the following method R is preferably 4 to 100%, more preferably 6 to 100%, and even more preferably 6 to 80%. R If the area ratio S of the aggregate (h2) is equal to or greater than the lower limit, the flowability of the resin mortar is good. R When the viscosity is equal to or less than the upper limit, the flowability of the resin mortar can be ensured to be good.
[0124] (Area ratio of aggregate (h2) S R (Calculation method) In the image analysis of the SEM images of the same field of view and the map data of silicon, iron, magnesium, and aluminum in the above steps (i) to (vi), the sum of the areas of the particles in the SEM images is defined as S SEM The sum of the areas of particles with a circularity of 0.85 or more in the map data of silicon, iron, magnesium, and aluminum is defined as S Si , S Fe , S Mg , S Al Then, the area ratio S is calculated from the following equation (4). R ' is calculated. S R '=(S Si +S Fe +S Mg +S Al ) / S SEM ×100...Formula (4) This procedure was carried out for SEM images of the same field of view for three different locations, as well as map data for silicon, iron, magnesium, and aluminum, and the area ratios S obtained for the three fields of view were calculated. R The average value of ' is calculated by the area ratio S of aggregate (h2) R Let us assume that.
[0125] Examples of aggregate (h2) having an average circularity of 0.85 or more include granulated slag, glass beads, hollow silica beads, fly ash, activated carbon with a high circularity produced from petroleum pitch, spherical aggregate for casting, alumina-based spherical low-expansion artificial sand, etc. One type of aggregate (h2) may be used alone, or two or more types may be used in combination.
[0126] [Aggregate (h3)] The aggregate (h3) having a particle diameter exceeding 300 μm may contain a coarse particle aggregate (hz) having a particle diameter exceeding 850 μm. In other words, the aggregate (H) may contain the coarse particle aggregate (hz) having a particle diameter exceeding 850 μm from the aggregate (h3) having a particle diameter exceeding 300 μm, and the proportion of the aggregate (h3) in the aggregate (H) may be 30 to 70 mass%.
[0127] In order to improve the fluidity of the resin mortar composition, the ratio of coarse particle size aggregate (hz) having a particle size of more than 850 μm and the ratio of aggregate having a particle size of more than 1,180 μm is 0 to 10 mass% out of 100 mass% of aggregate (H). It is also preferable that the ratio of coarse particle size aggregate (hz) having a particle size of more than 1,180 μm is 0 to 10 mass% out of 100 mass% of aggregate (H) and the ratio of aggregate having a particle size of more than 1,180 μm is 0 to 0.5 mass%. When an aggregate containing a large amount of coarse particle aggregate is mixed into a resin mortar composition, the flow is hindered by the coarse particle aggregate, making it difficult for the aggregate to wet and spread on the base.
[0128] Aggregate (H) can be classified into the following aggregates (H1) to (H9). These aggregates (H1) to (H9) are obtained by sieving aggregate (H) using sieves with nominal openings of 75μm, 106μm, 150μm, 300μm, 425μm, 600μm, 850μm, and 1,180μm as specified in JIS Z 8801-1. Aggregate (H1): Aggregate having a particle size of 75 μm or less in the aggregate (H) Aggregate (H2): Aggregate having a particle size of more than 75 μm and not more than 106 μm in the aggregate (H) Aggregate (H3): Aggregate having a particle size of more than 106 μm and not more than 150 μm in the aggregate (H) Aggregate (H4): Aggregate having a particle size of more than 150 μm and not more than 300 μm in the aggregate (H) Aggregate (H5): Aggregate having a particle size of more than 300 μm and not more than 450 μm in the aggregate (H) Aggregate (H6): Aggregate having a particle size of more than 450 μm and not more than 600 μm in the aggregate (H) Aggregate (H7): Aggregate having a particle size of more than 600 μm and not more than 850 μm in the aggregate (H) Aggregate (H8): Aggregate with a particle size of more than 850 μm and less than 1,180 μm in the aggregate (H) Aggregate (H9): Aggregate with a particle size of more than 1,180 μm in the aggregate (H)
[0129] The integrated value (S3) of the specific surface area of aggregate (h3) calculated by the following formula (1) is 25 to 70 cm 2 / g is preferred, and 25 to 65 cm 2 / g is more preferable, and 25 to 60 cm 2 / g is more preferable. If the integrated value (S3) of the specific surface area of the aggregate (h3) is equal to or greater than the lower limit, separation between the aggregate (H) and the resin component is less likely to occur, the coating thickness is easily ensured, and a good hardened coating film tends to be obtained. On the other hand, if the integrated value (S3) of the specific surface area of the aggregate (h3) is equal to or less than the upper limit, separation between the aggregate (H) and the resin component is less likely to occur, and the flowability of the resin mortar composition is also good.
[0130] S3=6 / (D1×d×W1 / 100)+6 / (D2×d×W2 / 100)+6 / (D3×d×W3 / 100)+6 / (D4×d×W4 / 100)+6 / (D5×d×W5 / 100)...Formula (1)
[0131] Here, the symbols in the formula (1) have the following meanings. S3: Accumulated value of specific surface area (cm 2 / g) D1 = 300 (μm) / 10000 = 0.03 (cm) D2 = 450 (μm) / 10000 = 0.045 (cm) D3 = 600 (μm) / 10000 = 0.06 (cm) D4 = 850 (μm) / 10000 = 0.085 (cm) D5 = 1180 (μm) / 10000 = 0.118 (cm) W1: Proportion of aggregate (H5) in aggregate (H) (mass%) W2: Proportion of aggregate (H6) in aggregate (H) (mass%) W3: Proportion of aggregate (H7) in aggregate (H) (mass%) W4: Proportion of aggregate (H8) in aggregate (H) (mass%) W5: Proportion of aggregate (H9) in aggregate (H) (mass%) d: Bulk density of aggregate (H) (g / cm 3 )
[0132] The bulk density (d) of aggregate (H) is determined by the following measurement method. (Method of measuring bulk density of aggregate) Pass the aggregate (H) gently through a sieve with 1.8 mm openings so as not to change its properties, and weigh out approximately 100 g with an accuracy of 0.1% to prepare a sample, whose mass is designated M (g). The sample is gently placed into a dry 250 mL graduated cylinder (minimum graduation unit: 2 mL) so as not to apply consolidation stress. At this time, tilt the graduated cylinder as necessary to gently pour the sample. Also, if necessary, carefully smooth the top surface of the aggregate layer without consolidating it. Read the filling volume (V0) of the sample in the graduated cylinder to the minimum graduation unit, and calculate the bulk density (d) (g / cm) from the following equation (2): 3 ) is calculated. d=M / V0... Formula (2)
[0133] The ratio R of the integrated value of the specific surface area (S3) to the integrated value (S) of the total specific surface area of the aggregate (H) calculated by the following formula (3) S3 The ratio R is preferably 3 to 16%, and more preferably 3.5 to 15.5%. S3 If the ratio R is equal to or greater than the lower limit, the influence of aggregates having fine particle diameters in the aggregate mixture is reduced, and the resin mortar does not thicken and has good fluidity. S3When the ratio is equal to or less than the upper limit, the influence of aggregates having a coarse particle size in the aggregate mixture is reduced, and the fluidity of the resin mortar is improved.
[0134] S=6 / (D6×d×W6 / 100)+6 / (D7×d×W7 / 100)+6 / (D8×d×W8 / 100)+6 / (D9×d×W9 / 100)+6 / (D 10 ×d×W 10 / 100)+6 / (D 11 ×d×W 11 / 100)+6 / (D 12 ×d×W 12 / 100)+6 / (D 13 ×d×W 13 / 100)+6 / (D 14 ×d×W 14 / 100)...Equation (3)
[0135] Here, the symbols in the formula (3) have the following meanings. S: Accumulated value of the total specific surface area of aggregate (H) (cm 2 / g) D6 = 50 (μm) / 10000 = 0.005 (cm) D7 = 75 (μm) / 10000 = 0.0075 (cm) D8 = 106 (μm) / 10000 = 0.0106 (cm) D9 = 150 (μm) / 10000 = 0.015 (cm) D 10 =300(μm) / 10000=0.03(cm) D 11 =450(μm) / 10000=0.045(cm) D 12 =600(μm) / 10000=0.06(cm) D 13 =850(μm) / 10000=0.085(cm) W6: Proportion of aggregate (H1) in aggregate (H) (mass%) W7: Proportion of aggregate (H2) in aggregate (H) (mass%) W8: Proportion of aggregate (H3) in aggregate (H) (mass%) W9: Proportion of aggregate (H4) in aggregate (H) (mass%) W 10 : Proportion of aggregate (H5) in aggregate (H) (mass%) W 11 : Proportion of aggregate (H6) in aggregate (H) (mass%) W 12 : Proportion of aggregate (H7) in aggregate (H) (mass%) W 13 : Proportion of aggregate (H8) in aggregate (H) (mass%) W 14 : Proportion of aggregate (H9) in aggregate (H) (mass%) d: Bulk density of aggregate (H) (g / cm 3 ) The bulk density (d) of the aggregate (H) can be determined from the above-mentioned formula (2) using the above-mentioned measurement method.
[0136] The total specific surface area (S) of the aggregate (H) is 350 to 5,000 cm 2 / g is preferred, and 350 to 2,000 cm 2 / g is more preferable, and 350 to 1,000 cm 2 / g is even more preferable. If the integrated value (S) of the total specific surface area of the aggregate (H) is equal to or greater than the lower limit, separation between the aggregate (H) and the resin component is unlikely to occur, the coating thickness is easily ensured, and a good hardened coating film tends to be obtained. On the other hand, if the integrated value (S) of the total specific surface area of the aggregate (H) is equal to or less than the upper limit, separation between the aggregate (H) and the resin component is unlikely to occur, and the flowability of the resin mortar composition is also good.
[0137] The content of the aggregate (H) is 50 to 2,000 parts by mass, preferably 100 to 1,000 parts by mass, and more preferably 200 to 800 parts by mass, based on 100 parts by mass of the resin composition (x).
[0138] The use of the resin mortar composition of the present invention is not particularly limited, and it can be suitably used for civil engineering and construction materials such as coating materials, floor coating materials, road surface paving materials, wall materials, and repair fillers. For example, if a coating material is produced using the resin mortar composition of the present invention as a coating material composition, the coating material has low flammability in addition to the inherent properties of acrylic coating material compositions, such as excellent low-temperature curing, weather resistance, and chemical resistance.
[0139] <Method of producing resin mortar composition> The resin mortar composition of the present invention can be produced, for example, by mixing the above-mentioned components with a commonly used mixer.
[0140] <Action and effect> The resin mortar composition of the present invention can be hardened in a short time under a wide range of temperature conditions from room temperature to low temperature, and while the applied resin mortar has excellent fluidity until it hardens, separation of the resin and aggregate is suppressed until the coating film hardens. In addition, the cured product of the resin mortar composition of the present invention has excellent mechanical properties and weather resistance, and can therefore be suitably used as a civil engineering and construction material such as a coating material, a floor coating material, a road surface paving material, a wall material, or a repair filler. Furthermore, the resin composition of the present invention can be injected or filled as a repair material for defective parts of roads to obtain a cured product that can be rapidly applied under a wide range of temperature conditions from room temperature to low temperature.
[0141] <Laminate> The laminate of the present invention comprises a substrate and a cured coating film made of a cured product of the resin mortar composition of the present invention provided on the substrate. The laminate of the present invention may comprise a cured coating film made of a cured product of a resin composition not containing aggregate used in the resin mortar composition of the present invention on the substrate, and may further comprise a cured coating film made of a cured product of the resin mortar composition of the present invention on the substrate. The laminate is obtained by applying the resin mortar composition of the present invention to the substrate and curing it to form a cured product.
[0142] Examples of the base include cement concrete, asphalt concrete, mortar concrete, resin concrete, water-permeable concrete, ALC (lightweight foamed concrete) boards, PC (precast concrete) boards, asphalt, asphalt concrete, semi-flexible pavement, etc. These may be used alone or in combination of two or more types to form the base. The concrete may or may not contain reinforcing bars. The base can be used for floor slab structures such as building floors, platforms, roads, bridges, and viaducts, and can be used for applications aimed at stabilizing structures, such as repairing road ruts, repairing road defects, correcting road steps, adjusting the height of railway track slabs, preventing track slabs from being shaken when trains pass by, preventing rainwater from entering, and preventing the scattering of cement asphalt mortar that has been crushed due to weathering, etc. The shape of the substrate is not particularly limited and may be any shape, such as a flat surface, a curved surface, or an inclined surface.
[0143] The cured coating film is a cured product of the resin mortar composition of the present invention. The cured coating film is not particularly limited, except that it is a cured product of the resin mortar composition of the present invention. The thickness of the cured coating film of the present invention is preferably 0.03 to 5 cm, more preferably 0.03 to 2 cm, and even more preferably 0.05 to 1 cm. When the thickness of the cured coating film is equal to or greater than the lower limit, the surface of the cured coating film is less likely to become sticky. When the thickness of the cured coating film is equal to or less than the upper limit, the surface of the cured coating film is less likely to become sticky.
[0144] The method for forming the cured coating film includes a method in which the resin mortar composition of the present invention is applied to a substrate and then cured. Examples of the coating method include known coating methods using a roller, a metal trowel, a brush, a flexible broom, a coating machine (such as a lysine gun), and the like.
[0145] The surface temperature of the substrate when the resin mortar composition of the present invention is applied onto the substrate is preferably −20 to 65° C., more preferably −10 to 60° C., and even more preferably −10 to 55° C. If the surface temperature of the substrate is within the above range, coating using the resin mortar composition becomes possible under a wide range of temperature conditions from room temperature to low temperature.
[0146] From the viewpoint of workability, the pot life is preferably from 10 to 60 minutes, more preferably from 10 to 45 minutes, and even more preferably from 15 to 30 minutes. The curing time is preferably from 10 to 120 minutes, more preferably from 15 to 90 minutes, and further preferably from 20 to 60 minutes. The pot life and curing time are adjusted by appropriately adjusting the amounts of the organic peroxide curing agent and curing accelerator used. EXAMPLES
[0147] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following examples, all "parts" mean "parts by mass", and all "%" other than those for saponification degree and humidity mean "% by mass".
[0148] <abbreviation> The abbreviations for the materials used in the examples are shown below. i-BMA: i-butyl methacrylate (product name: Acryester IB, manufactured by Mitsubishi Chemical Corporation, flash point: 45°C (value listed in SDS), cited SDS revision date: April 1, 2017) n-BMA: n-butyl methacrylate (product name: Acryester B, manufactured by Mitsubishi Chemical Corporation, flash point: 51°C (value listed in SDS), cited SDS revision date: April 1, 2017) 2-EHA: 2-ethylhexyl methacrylate (Mitsubishi Chemical Corporation, flash point: 86°C (value listed in SDS), reference SDS revision date: June 2, 2012) DH500: Dicyclopentenyloxyethyl methacrylate (manufactured by Hitachi Chemical Co., Ltd., flash point: 176°C (value listed on the website)) MMA: Methyl methacrylate (Mitsubishi Chemical Corporation, flash point: 11°C (SDS listed value), cited SDS revision date: April 1, 2021) 2-HEMA: 2-hydroxyethyl methacrylate (product name: Acryester HO, manufactured by Mitsubishi Chemical Corporation, flash point: 109°C (value listed in SDS), cited SDS revision date: April 1, 2017) 2-HPMA: 2-hydroxypropyl methacrylate (Mitsubishi Chemical Corporation, flash point: 106°C (value listed in SDS), cited SDS revision date: April 1, 2017) 4-HBA: 4-hydroxybutyl acrylate (product name: 4HBA, manufactured by Osaka Organic Chemical Industry Co., Ltd., flash point: 134°C (value listed in SDS), cited SDS revision date: April 15, 2013) A-SA: 2-Succinoyloxyethyl acrylate (product name: NK Ester A-SA, manufactured by Shin-Nakamura Chemical Co., Ltd., flash point: 178°C (value listed in SDS), cited SDS revision date: June 13, 2016) BDMA: 1,4-butanediol dimethacrylate M2101: Bisphenol A type ethylene oxide modified dimethacrylate (product name: Miramer M2101, manufactured by Miwon, flash point: 250°C or higher (value listed in SDS), reference SDS revision date: August 17, 2017) SUA-017: Urethane acrylate (product name: EXCELATE SUA-017, manufactured by Asia Industries Co., Ltd., flash point: 130°C (solidification) (value listed in SDS), cited SDS revision date: August 6, 2016) PU2560: Urethane acrylate (product name: MIRAMER PU2560, manufactured by MIWON, flash point: 210°C (value listed in SDS), cited SDS revision date: January 13, 2016) Mesamol: Alkyl sulfonate ester plasticizer (product name: Mesamoll, manufactured by LANXESS KK) P-1: Acrylic polymer (P-1) obtained in Synthesis Example 1 described below P-2: Acrylic polymer (P-2) obtained in Synthesis Example 2 described below DMPT: N,N-dimethyl-p-toluidine (trade name: DMPT, manufactured by Samsung Chemical Research Institute Co., Ltd.) DIPT: N,N-di(2-hydroxypropyl)-p-toluidine (product name: DIPT, manufactured by Nippon Nyukazai Co., Ltd.) PTEO: N,N-di(2-hydroxyethyl)-p-toluidine (product name: PTEO, manufactured by Nippon Nyukazai Co., Ltd.) P-115: Paraffin wax with a melting point of 55°C (product name: Paraffin Wax 115, manufactured by Nippon Seiro Co., Ltd.) P-130: Paraffin wax with a melting point of 66°C (product name: Paraffin Wax 130, manufactured by Nippon Seiro Co., Ltd.) P-150: Paraffin wax with a melting point of 75°C (product name: Paraffin Wax 150, manufactured by Nippon Seiro Co., Ltd.) HQ: Hydroquinone MEHQ: 4-Methoxyphenol AMBN: 2,2'-azobis-2-methylbutyronitrile n-DM: n-dodecyl mercaptan KBM-503: 3-methacryloxypropyltrimethoxysilane (product name: KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) 230EF: Defoamer (product name: Disparlon 230EF, manufactured by Kusumoto Chemicals Co., Ltd.) BYK-352: Product name: BYK-352, manufactured by BYK D-2164: Product name: DISPERBYK-2164, manufactured by BYK GB-50L: Product name: Percadox GB-50L, manufactured by Nouryon Chemical Co., Ltd. (50% purity of benzoyl peroxide) CO-12E: Cobalt 2-ethylhexanoate (product name: CO-12E, manufactured by Tokyo Fine Chemical Co., Ltd.) AC-103: Curing accelerator (product name: ACRYSIRUP AC-103, manufactured by Mitsubishi Chemical Infratec Co., Ltd.) K-80: Cumene hydroperoxide (product name: Trigonox K-80, manufactured by Kayaku Nouryon Co., Ltd.)
[0149] [Synthesis Example 1: Synthesis of acrylic polymer (P-1)] In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 135 parts of deionized water and 0.4 parts of polyvinyl alcohol (saponification degree 80 mol%, polymerization degree 1,700) as a dispersant were added and stirred, and after the polyvinyl alcohol was completely dissolved, stirring was stopped once. 40 parts of MMA, 60 parts of n-BMA, 0.2 parts of AMBN as a polymerization initiator, 0.5 parts of n-DM as a chain transfer agent, and 0.1 parts of sodium carbonate as an electrolyte were added and stirred again, and the temperature was raised to 75 ° C. and reacted for 2.5 hours. The temperature was further raised to 98 ° C. and maintained for 1.5 hours, after which the reaction was terminated. Next, after cooling to 40°C, the resulting aqueous suspension was filtered through a nylon filter cloth with 45 μm mesh, and the filtrate was washed with deionized water, dehydrated, and then dried at 40°C for 16 hours to obtain a granular acrylic polymer (P-1). The resulting acrylic polymer (P-1) had a Tg of 49° C. and a Mw of 60,000.
[0150] [Synthesis Example 2: Synthesis of acrylic polymer (P-2)] In the reaction of Synthesis Example 1, the amount of MMA used was changed from 40 parts to 60 parts, the amount of n-BMA used was changed from 60 parts to 40 parts, and the amount of n-DM used was changed from 0.5 parts to 0.8 parts. Other than that, the same procedure as in Synthesis Example 1 was followed to obtain a granular acrylic polymer (P-2) having a Tg of 64°C and a Mw of 40,000.
[0151] <Preparation of Resin Composition> [Preparation of resin composition (S-1)] In a 1L flask equipped with a stirrer, thermometer, and cooling tube, 57.0 parts of i-BMA as component (A), 15.0 parts of 4-HBA, 20.0 parts of SUA-017 as component (B), 0.01 parts of MEHQ as a light stabilizer, 0.5 parts of KBM-503 as a silane coupling agent, 0.5 parts of P-115, 0.4 parts of P-130, and 0.3 parts of P-150 as waxes, 0.5 parts of 230EF as an antifoaming agent, 0.5 parts of D-2164 as a wetting dispersant, and 0.4 parts of PTEO as a curing accelerator were added, and then 12.0 parts of acrylic polymer (P-1) was added as component (b3) while stirring. Subsequently, the mixture was heated at 70°C for 2 hours to dissolve. After confirming dissolution, the mixture was cooled to obtain a resin composition (S-1). The composition of the resulting resin composition (S-1) is shown in Table 1.
[0152] [Preparation of resin compositions (S-2) to (S-4)] Resin compositions (S-2) to (S-4) were obtained in the same manner as for resin composition (S-1), except that the blending composition was changed to the composition shown in Table 1. The blending compositions of the obtained resin compositions (S-2) to (S-4) are shown in Table 1.
[0153] [viscosity] The viscosity of each resin composition was measured at 23±1° C. and 60 rpm using a Brookfield type viscometer (TVB-10M, manufactured by Toki Sangyo Co., Ltd.) with a TM1 rotor according to JIS Z 8803. The results are shown in Table 1.
[0154] [Flammability] Among the radical polymerizable compounds contained in each resin composition at 5% by mass or more, the flash point of the radical polymerizable compound with the lowest flash point was defined as the minimum flash point, and flammability was evaluated according to the following evaluation criteria. The results are shown in Table 1. For the flash point of each radical polymerizable compound, the values listed in the SDS issued by each manufacturer or on their websites were used. (Evaluation Criteria) ◎: Minimum flash point is 35℃ or higher 〇: Minimum flash point is 25℃ or higher and less than 35℃ △: Minimum flash point is 15℃ or higher and less than 25℃ ×: Minimum flash point is less than 15℃
[0155] [Mechanical properties] Each resin composition was poured into a cell cast and cured in an environment of 23°C. The cured resin product, cured to a thickness of 3 mm, was molded into five dumbbell-shaped No. 1 pieces using a punch specified in JIS K 6251 "Vulcanized rubber and thermoplastic rubber." Tensile tests were carried out on the five molded test pieces using a tensile tester (manufactured by A&D Co., Ltd., product name: "Tensilon Universal Tensile Tester") to measure the elongation at break (%) and evaluate the mechanical properties according to the following evaluation criteria. The results are shown in Table 1. Note that although the tensile speed specified in JIS K 6251 is 500 mm / min, in this example, the test was carried out at a tensile speed of 20 mm / min. (Evaluation Criteria) ◎: Elongation at break is 200% or more ○: Elongation at break is 100% or more but less than 200% ×: Elongation at break is less than 100%
[0156] [Table 1]
[0157] <Preparation of aggregate> Aggregates (K-1) to (K-12) were prepared by blending the aggregates so that the particle size distribution in Table 2 would be obtained when the aggregates were sieved. As aggregate (K-7), KS-1 (Mitsubishi Chemical Infratec Corp. aggregate) described in Example 11 of JP 2015-229683 A was used.
[0158] [Sieving aggregates] The sieving of the aggregate was carried out using sieves with nominal openings of 75 μm, 106 μm, 150 μm, 300 μm, 425 μm, 600 μm, 850 μm, 1,180 μm, and 1,700 μm as specified in JIS Z 8801-1, in accordance with the method specified in "Test method for sieving of aggregates" in JIS A 1102:2014.
[0159] [Aggregate particle size] The aggregate remaining on each sieve when the above-mentioned "sieving of aggregate" was carried out was treated as the aggregate particle size, and the aggregate particle sizes shown in Table 2 were defined as follows: Particle size PAN~75μm: Aggregate that passed through a sieve with a mesh size of 75μm. In the formula for calculating the specific surface area, the aggregate particle size was set to 50μm. However, "PAN" refers to the particle size of the particles remaining in the sieve tray. Particle size 75~106μm: Aggregate on a sieve with 75μm openings. In calculating the specific surface area, the aggregate particle size was set to 75μm. Particle size 106~150μm: Aggregate on a sieve with an opening of 106μm. In calculating the specific surface area, the aggregate particle size was set to 106μm. Particle size 150-300μm: Aggregate on a sieve with 150μm openings. In calculating the specific surface area, the aggregate particle size was set to 150μm. Particle size 300~425μm: Aggregate on a sieve with 300μm openings. In calculating the specific surface area, the aggregate particle size was set to 300μm. Particle size 425~600μm: Aggregate on a sieve with an opening of 425μm. In calculating the specific surface area, the aggregate particle size was set to 425μm. Particle size 600~850μm: Aggregate on a sieve with an opening of 600μm. In calculating the specific surface area, the aggregate particle size was set to 600μm. Particle size 850~1,180μm: Aggregate on a sieve with an opening of 850μm. In calculating the specific surface area, the aggregate particle size was set to 850μm. Particle size 1,180~1,700μm: Aggregate on a sieve with an opening of 1,180μm. In calculating the specific surface area, the aggregate particle size was set to 1,180μm. Particle size 1,700μm or more: Aggregate on a sieve with an opening of 1,700μm. In calculating the specific surface area, the aggregate particle size was set to 1,700μm.
[0160] [Table 2]
[0161] [Aggregate evaluation] For aggregates (K-1) to (K-12), the bulk density (d), the total aggregate specific surface area (S), the total aggregate specific surface area (S3) of aggregates (h3) with particle diameters exceeding 300 μm, and the ratio R of the specific surface area (S3) of aggregates (h3) with particle diameters exceeding 300 μm. S3 , the proportion of coarse aggregate (hz) with a particle diameter exceeding 1,180 μm and aggregate with a particle diameter exceeding 850 μm, the proportion of aggregate (h3) with a particle diameter exceeding 300 μm, the proportion of aggregate (h1) with a particle diameter of 300 μm or less, and the area ratio S of aggregate (h2) with an average circularity ratio of 0.85 or more R was measured by the method described above, and the results are shown in Table 3. The proportion of aggregate (h3) with a particle diameter exceeding 300 μm was determined as the integrated value of the proportions of aggregates (H5) to (H8), (H9-1), and (H9-2) in Table 2. The proportion of aggregate (h1) with a particle size of 300 μm or less was determined as the integrated value of the proportions of aggregates (H1) to (H4) in Table 2. The proportion of aggregates with a particle size exceeding 1,180 μm was determined as the integrated value of the proportions of aggregates (H9-1) and (H9-2) in Table 2. For aggregates with a particle size exceeding 850 μm, the integrated value of the proportions of aggregates (H8), (H9-1) and (H9-2) was used.
[0162] [Table 3]
[0163] In addition, in the image analysis of the circularity measurement of aggregate (h1) having a particle diameter of 300 μm or less of aggregate (K-3), Figures 1 to 7 show the SEM image before processing, after Gaussian filter processing, after binarization processing, after edge shaping, after hole filling processing, after division processing, and the measurement image, and Figures 8 to 15 show the EDS map data (silicon is used as an example here) before processing, after 8-bit conversion, after Gaussian filter processing, after binarization processing, after edge shaping, after hole filling processing, after division processing, and the measurement image.
[0164] [Example 1] Using a mixer, 100 parts of the resin composition (S-1), 525 parts of the aggregate (K-1), and 2 parts of GB-50L were mixed to obtain a resin mortar composition.
[0165] [Examples 2 to 3, Examples 6 to 7] Except for changing the blending composition as shown in Table 4, the same procedure as in Example 1 was carried out to obtain a resin mortar composition.
[0166] [Comparative Examples 1 to 6, Comparative Examples 10 to 11] Except for changing the blending composition as shown in Table 4, the same procedure as in Example 1 was carried out to obtain a resin mortar composition.
[0167] <Evaluation 2> [Flow Area] To measure the flow area, a flow cone (upper inner diameter of the cone: 70.0 ± 0.5 mm, lower inner diameter of the cone: 100.0 ± 0.5 mm, cone height: 60.0 ± 0.5 mm) as described in JIS R 5201:2015, “Physical Testing Methods for Cement” was used. In an environment of 23°C, a PET film of 40 cm or more square was laid, and the resin mortar composition described in Table 4 containing the hardener was filled in two layers in a flow cone placed correctly in the center of the PET film. Each layer was poked 15 times over the entire surface so that the tip of the poker penetrated to about 1 / 2 the depth of the layer, and finally, if necessary, the deficiency was supplemented and the surface was smoothed. The flow cone was immediately removed vertically and left to stand. When the resin mortar composition lost its fluidity, it was measured to the nearest 0.1 cm in the "direction in which the diameter of the resin mortar composition after spreading was recognized as the maximum" and in the "direction perpendicular to this" and the flow area was calculated by the following formula (11). Flow area = (L1 / 2) × (L2 / 2) × π Equation (11) L1: The dimension in the direction in which the diameter after the resin mortar composition spreads is recognized as the maximum L2: Dimension in the direction perpendicular to the "direction in which the diameter is recognized as the maximum" after the resin mortar composition has spread π: Pi The test was carried out twice, and the average value was calculated as the flow area in integer units and evaluated according to the following evaluation criteria. The results are shown in Table 4. (Evaluation Criteria) ◎: Flow area is 900cm 2 Exceed ○: Flow area is 650~900cm 2 ×: Flow area is 650cm 2 less than
[0168] [Separation of resin and aggregate] When the flow area was evaluated, the outer periphery of the flow cone was visually inspected at the time when the resin mortar composition lost its fluidity to check whether separation of the resin component and aggregate was observed, and the evaluation was performed according to the following evaluation criteria. The results are shown in Table 4. (Evaluation Criteria) ○: No separation observed ×: Separation is observed
[0169] [Surface hardening] When the resin mortar composition was cured in the above-mentioned evaluation of the flow area, the touch dryness of the coating surface was checked 1 hour after the addition of the curing agent, and evaluated according to the following evaluation criteria. The results are shown in Table 4. (Evaluation Criteria) ○: The coating surface becomes sticky within 60 minutes ×: Stickiness remains on the coating surface within 60 minutes ××: Within 60 minutes, liquid uncured material remains on the coating surface and the coating does not cure.
[0170] <Evaluation 3> [Bending test] The bending test was conducted with reference to JIS K7171:2016 "Determination of bending properties of plastics," except that the measurement temperature was 23°C, the test speed was 2 mm / min, and the distance between supports was 8 times the thickness of the strip made of resin mortar.
[0171] Bending stress δ f The value was calculated by the following formula (12) and evaluated according to the following evaluation criteria. The results are shown in Table 4. Bending stress δ f (MPa) = 3FL / (2bh 2 )...Equation (12) δ f : Bending stress (MPa) F: Force (N) L: Distance between fulcrums (mm) b: Average width of the test piece (mm) h: average thickness of the test piece (mm) (Evaluation Criteria) ◎: Bending stress exceeds 15MPa ○: Bending stress is 10 to 15 MPa ×: bending stress is less than 10 MPa
[0172] Bending strain ε f was calculated using the following formula (13) and evaluated according to the following evaluation criteria. The results are shown in Table 4. Bending strain ε f (%)=600sh / L 2 ...Equation (13) ε f : Bending strain (%) s: Deflection (mm) h: average thickness of the test piece (mm) L: Distance between fulcrums (mm) (Evaluation Criteria) ◎: Bending strain exceeds 7% 〇: Bending strain is 5-7% ×: bending strain less than 5%
[0173] [Table 4]
[0174] As shown in Table 4, the resin mortar compositions prepared in Examples 1 to 3 and Examples 6 to 7 had high fluidity and a good flow area. On the other hand, the proportion of aggregates with particle diameters exceeding 1,180 μm, the proportion of aggregates with particle diameters exceeding 850 μm, the integrated value (S3) of the specific surface area of the aggregate (h3), and the ratio R of the integrated value (S3) of the specific surface area S3The resin mortar compositions of Comparative Examples 1 to 6 and Comparative Examples 10 to 11, which did not satisfy any one or more of the above conditions, had low fluidity and did not provide a sufficient flow area. The bending strains of Comparative Examples 1, 2, and 4 to 6 were also low. Separation of the resin component and aggregate was observed in Comparative Example 4, and surface hardening properties were poor in Comparative Examples 5 and 6.
[0175] [Example 4] Using a mixer, 100 parts of the resin composition (S-2), 525 parts of the aggregate (K-1), and 2 parts of GB-50L were mixed to obtain a resin mortar composition. The temperature of the substrate was set at 23°C, and the resin mortar composition was applied to the substrate with a flexible broom to a thickness of 5 mm to obtain a laminate.
[0176] [Comparative Examples 7 to 9] A laminate was obtained in the same manner as in Example 4, except that the composition of the resin mortar composition was changed to that shown in Table 5.
[0177] [Example 5] Using a stirrer, 100 parts of the resin composition (S-2), 525 parts of the aggregate (K-1), and 1.2 parts of GB-50L were mixed to obtain a resin mortar composition. The temperature of the base was set to 62°C, and the resin mortar composition was applied to the base with a flexible broom to a thickness of 5 mm to obtain a laminate.
[0178] [Example 8] A resin mortar composition was obtained by mixing 100 parts of resin composition (S-2), 525 parts of aggregate (K-3), 5 parts of hardening accelerator AC-103, and 10 parts of hardener GB-50L with a stirrer in a thermostatic chamber adjusted to a temperature of -15°C. The temperature of the substrate was adjusted to -15°C in the thermostatic chamber, and the resin mortar composition was applied to the substrate with a flexible broom to a thickness of 5 mm to obtain a laminate.
[0179] <Rating 4> [Paintability evaluation] The laminates of each example were evaluated for workability, appearance, and surface hardening properties according to the following criteria. The results are shown in Table 5. (Workability) ○: Easy to paint △: Some resistance is felt when painting ×: Resistance is felt when painting and it is difficult to paint evenly
[0180] (exterior) ○: After curing, the marks left by the brush flow away and do not remain. △: After hardening, the appearance shows some traces of the paint applied with a brush. ×: After curing, the appearance shows a lot of traces left by the brush.
[0181] (Surface hardening) When the resin mortar composition was cured, the touch dryness of the coating surface was checked 1 hour after the addition of the curing agent, and evaluated according to the following evaluation criteria. The results are shown in Table 5. ○: The coating surface becomes sticky within 60 minutes ×: Stickiness remains on the coating surface within 60 minutes ××: Within 60 minutes, liquid uncured material remains on the coating surface and the coating does not cure.
[0182] [Table 5]
[0183] As shown in Table 5, the resin mortar compositions of Examples 4, 5 and 8 had excellent workability, appearance and surface curing properties even when the temperature of the substrate changed during coating. On the other hand, the ratio of aggregates with particle diameters exceeding 1,180 μm, the ratio of aggregates with particle diameters exceeding 850 μm, and the ratio of the integrated value of the specific surface area (S3) R S3 The resin mortar compositions of Comparative Examples 7 to 9, which did not satisfy any one or more of the above conditions, exhibited poor workability when applied to a substrate and also had poor appearance. [Industrial Applicability]
[0184] The resin mortar composition of the present invention can be hardened in a short time under a wide range of temperature conditions from room temperature to low temperature, and while the applied resin mortar has excellent fluidity until it hardens, separation of the resin and aggregate is suppressed until the coating film hardens. Furthermore, the cured product of the resin mortar composition of the present invention has excellent mechanical properties and weather resistance, and can therefore be suitably used as a civil engineering and construction material such as a coating material, a floor coating material, a road surface paving material, a wall material, or a repair filler. In addition, the resin mortar composition of the present invention can be injected or filled as a repair material for defective parts of roads to obtain a hardened product that can be quickly applied under a wide range of temperature conditions from room temperature to low temperature, and is therefore extremely important from an industrial perspective.
Claims
1. A resin mortar composition comprising 100 parts by mass of a resin composition (x) and 50 to 2,000 parts by mass of an aggregate (H), In 100% by mass of the aggregate (H), the proportion of aggregate having a particle diameter exceeding 1,180 μm is 0 to 1% by mass, the proportion of aggregate having a particle diameter exceeding 850 μm is 0 to 10% by mass, and the proportion of aggregate (h3) having a particle diameter exceeding 300 μm is 30 to 70% by mass; The integrated value (S3) of the specific surface area of the aggregate (h3) calculated by the following formula (1) is 25 to 70 cm 2 / g, The ratio R of the integrated value (S3) of the specific surface area to the integrated value (S) of the total specific surface area of the aggregate (H) calculated by the following formula (3) S3 The resin mortar composition according to claim 1, S3 = 6 / (D 1 × d × W 1 / 100) + 6 / (D 2 × d × W 2 / 100) + 6 / (D 3 × d × W 3 / 100) + 6 / (D 4 × d × W 4 / 100) + 6 / (D 5 × d × W 5 / 100) ··· Equation (1) (In the above formula (1), S3 is the integrated value of the specific surface area (cm 2 / g), and D 1 =300(μm) / 10000=0.03(cm), D 2 =450(μm) / 10000=0.045(cm), D 3 =600(μm) / 10000=0.06(cm), D 4 =850(μm) / 10000=0.085(cm), D 5 = 1180 (μm) / 10000 = 0.118 (cm). 1 ~W 5 are the proportions (mass%) of the aggregates (H5) to (H9) in the aggregate (H), respectively. d is the bulk density (g / cm 3 ) and can be determined by the following method for measuring the bulk density of aggregate.) S = 6 / (D 6 × d × W 6 / 100) + 6 / (D 7 × d × W 7 / 100) + 6 / (D 8 × d × W 8 / 100) + 6 / (D 9 × d × W 9 / 100) + 6 / (D 10 × d × W 10 / 100) + 6 / (D 11 × d × W 11 / 100) + 6 / (D 12 × d × W 12 / 100) + 6 / (D 13 × d × W 13 / 100) + 6 / (D 14 × d × W 14 / 100) ··· Equation (3) (In the above formula (3), S is the integrated value (cm) of the total specific surface area of the aggregate (H). 2 / g), and D 6 =50(μm) / 10000=0.005(cm), D 7 =75(μm) / 10000=0.0075(cm), D 8 =106(μm) / 10000=0.0106(cm), D 9 =150(μm) / 10000=0.015(cm), D 10 =300(μm) / 10000=0.03(cm), D 11 =450(μm) / 10000=0.045(cm), D 12 =600(μm) / 10000=0.06(cm), D 13 = 850 (μm) / 10000 = 0.085 (cm). 6 ~W 14 are the proportions (mass%) of the aggregates (H1) to (H9) in the aggregate (H), respectively. d is the bulk density (g / cm 3 ) and can be determined by the following method for measuring the bulk density of aggregate.) Aggregate (H1): Aggregate having a particle size of 75 μm or less in the aggregate (H) Aggregate (H2): Aggregate having a particle size of more than 75 μm and not more than 106 μm in the aggregate (H) Aggregate (H3): aggregate having a particle size of more than 106 μm and not more than 150 μm in the aggregate (H) Aggregate (H4): Aggregate having a particle size of more than 150 μm and not more than 300 μm in the aggregate (H). Aggregate (H5): aggregate having a particle diameter of more than 300 μm and not more than 450 μm in the aggregate (H) Aggregate (H6): aggregate having a particle size of more than 450 μm and not more than 600 μm in the aggregate (H) Aggregate (H7): aggregate having a particle diameter of more than 600 μm and not more than 850 μm in the aggregate (H) Aggregate (H8): Aggregate having a particle size of more than 850 μm and not more than 1,180 μm in the aggregate (H). Aggregate (H9): Aggregate having a particle diameter of more than 1,180 μm in the aggregate (H) (Method of measuring bulk density of aggregate) The aggregate (H) is gently passed through a sieve with 1.8 mm openings so as not to change its properties, and about 100 g is weighed out with an accuracy of 0.1% to prepare a sample, and the mass of the sample is designated as M (g). The sample was gently placed in a dry 250 mL measuring cylinder (minimum graduation unit: 2 mL) without applying compression stress, and the filling volume (V 0 ) to the smallest scale unit, and calculate the bulk density (d) (g / cm) from the following formula (2): 3 ) is calculated. d = M / V 0 ・・・ Formula (2)
2. In 100% by mass of the aggregate (H), the ratio of aggregate (h1) having a particle diameter of 300 μm or less is 30 to 70% by mass, The aggregate (h1) includes the following aggregate (h2): The area ratio S of the aggregate (h2) calculated by the following calculation method R The resin mortar composition according to claim 1, wherein the content is 4 to 100%. Aggregate (h2): An aggregate in which, when the image analysis described below is performed, the average circularity of all components of silicon, iron, magnesium, and aluminum analyzed by image analysis is 0.85 or more. (Image analysis) A SEM (scanning electron microscope) image of the aggregate (h1) is taken, and elemental analysis is performed by EDS (energy dispersive X-ray spectroscopy) analysis for the same field of view of the SEM image, mapping is performed for each of silicon, iron, magnesium, and aluminum that constitute the aggregate, and image analysis is performed using image processing software ImageJ (manufactured by the National Institutes of Health) in the following steps (i) to (vi). Image analysis is performed using images converted to 8-bit map data. (i) Noise removal is performed using a Gaussian filter. (ii) A binarization process is performed to generate a binary image. (iii) The edges are smoothed using morphological operations. (iv) A filling process is carried out. (v) Perform the division process. (vi) Obtaining the area and circularity of the extracted particles. The image analysis is carried out three times, and the average value of the circularity values obtained is defined as the "average circularity." (Area ratio S of aggregate (h2) R (Calculation method) In the image analysis of the steps (i) to (vi) for the SEM image and the map data of silicon, iron, magnesium, and aluminum in the same field of view, the total area of the particles in the SEM image is S SEM The sum of the areas of particles with a circularity of 0.85 or more in the map data of silicon, iron, magnesium, and aluminum is defined as S. Si , S Fe , S Mg , S Al Then, the area ratio S is calculated from the following formula (4): R The same operation is carried out in three identical visual fields, and the area ratio S R The average value of ' is the area ratio S of the aggregate (h2). R Let us assume that. S R '=(S Si +S Fe +S Mg +S Al ) / S SEM ×100 ・・・Formula (4)
3. The resin mortar composition according to claim 1 or 2, wherein the resin composition (x) comprises at least one selected from the group consisting of acrylic resins and vinyl ester resins.
4. The resin mortar composition according to claim 1 or 2, wherein the viscosity of the resin composition (x) measured at 23 ° C. using a Brookfield viscometer (BM type) in accordance with JIS Z 8803 is 5 to 1,000 mPa · s.
5. The resin mortar composition according to claim 1 or 2, further comprising an organic peroxide.
6. A method for producing a laminate, comprising coating the resin mortar composition according to claim 5 on a substrate and curing the resin mortar composition.
7. A laminate comprising a substrate and a cured coating film formed on the substrate, the cured coating film being made of the resin mortar composition according to claim 5.
Citation Information
Patent Citations
Curable composition and composition for road marking using the same
JP1996209058A
Resin mortar composition and coated material
JP2013007000A
Packing material composition, and method for repairing cement asphalt mortar layer of slab track by using the composition
JP2015098527A
Syrup composition, syrup blended composition, laminate and production method of the laminate
JP2015229683A